Positive electrode material composition, its manufacturing method, and positive electrode sheet, secondary battery, and power consumption device including the same

The core-shell structured lithium manganese phosphate cathode active material, doped and coated with specific elements and organopolysiloxane, addresses manganese ion elution issues, enhancing the performance of secondary batteries in terms of energy density, cycle life, and safety.

JP2025500839AActive Publication Date: 2025-01-15CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024535302
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-06-24
Publication Date
2025-01-15
Estimated Expiration
2042-06-24

AI Technical Summary

Technical Problem

Lithium manganese phosphate cathode active materials in secondary batteries suffer from manganese ion elution during charging and discharging, leading to capacity loss, safety issues, and reduced electrochemical performance.

Method used

A positive electrode material composition with a core-shell structure, incorporating lithium manganese phosphate doped with specific elements and coated with pyrophosphate and phosphate layers, combined with an organopolysiloxane compound, to suppress manganese ion elution and enhance lithium ion mobility.

Benefits of technology

The solution results in improved energy density, cycle performance, safety, and rate performance of secondary batteries by reducing manganese ion elution and electrolyte erosion, while maintaining high lithium ion conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500839000001_ABST
    Figure 2025500839000001_ABST
Patent Text Reader

Abstract

The present application provides a positive electrode material composition, a method for producing the same, and a positive electrode sheet, a secondary battery, and a power consuming device each including the same. The positive electrode material composition includes a positive electrode active material having a core-shell structure and an organopolysiloxane compound, where the positive electrode active material includes a core and a shell covering the core, and the core is Li 1+x Mn 1-y A y P 1-z R z O4, and the shell includes a first coating layer that coats the core and a second coating layer that coats the first coating layer. The positive electrode material composition of the present application allows a secondary battery to have high energy density and simultaneously improve cycle performance, safety performance, and / or rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the technical field of batteries, and in particular to a positive electrode material composition, a manufacturing method thereof, and a positive electrode sheet, a secondary battery, and a power consuming device containing the same. [Background technology]

[0002] In recent years, secondary batteries have been widely used in many fields, such as energy storage power systems for hydroelectric, thermal, wind and solar power plants, electric tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, etc. With the application and popularity of secondary batteries, their safety performance has been attracting more and more attention. Lithium manganese phosphate has the advantages of large capacity, excellent safety performance, and abundant raw material supply sources, making it one of the most popular positive electrode active materials at present, but lithium manganese phosphate is prone to manganese ion elution during charging, which causes rapid capacity decay. Summary of the Invention

[0003] The present application aims to provide a positive electrode material composition, a method for producing the same, and a positive electrode sheet, a secondary battery, and a power consuming device each including the same, so that a secondary battery using the positive electrode material composition has a high energy density and also has improved cycle performance, safety performance, and / or rate performance.

[0004] A first aspect of the present application is a positive electrode material composition including a positive electrode active material having a core-shell structure and an organopolysiloxane compound, the positive electrode active material including a core and a shell covering the core, the core being Li 1+x Mn 1-y A y P 1-z R z O 4wherein x is −0.100 to 0.100, and optionally −0.100 to 0.006; y is 0.001 to 0.500, and optionally 0.100 to 0.450; z is 0.001 to 0.100; A is one or more selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and optionally one or more of Fe, Ti, V, Ni, Co, and Mg; R is one or more selected from B, Si, N, and S; the shell includes a first coating layer coating the core and a second coating layer coating the first coating layer, and the first coating layer is a pyrophosphate MP 2 O 7 and phosphate XPO 4 wherein M and X are each independently one or more selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and the second coating layer provides a positive electrode material composition including carbon.

[0005] In the present application, by doping lithium manganese phosphate with a specific element and coating the surface, it is possible to effectively suppress the elution of manganese ions during the lithium insertion and desorption process while promoting the movement of lithium ions. When the positive electrode active material of the present application is used in combination with an organopolysiloxane compound, it is possible to mitigate the erosion of the electrolyte on the surface of the positive electrode active material and reduce the elution of manganese ions, which is advantageous for improving the electrochemical performance of the positive electrode active material. Therefore, a power consumption device such as a positive electrode sheet and a secondary battery using the positive electrode material composition of the present application can combine high energy density and improved cycle performance, safety performance, and / or rate performance.

[0006] In any embodiment of the present application, the organopolysiloxane compound comprises at least one structural unit represented by formula 1:

number

[0007] This further reduces the elution of manganese ions, and significantly improves the cycle performance and / or high-temperature stability of the secondary battery.

[0008] In any embodiment of the present application, the organopolysiloxane compound includes one or more selected from polysiloxanes having a linear structure and polysiloxanes having a cyclic structure, and optionally, the organopolysiloxane compound is selected from polysiloxanes having a linear structure.

[0009] This further alleviates the corrosion of the surface of the positive electrode active material by the acidic substance in the electrolyte, reduces the elution of manganese ions, and significantly improves the cycle performance and storage performance of the secondary battery. Since the electrons in the rings of the cyclic polysiloxane have a certain degree of delocalization, the Si-O skeleton has a low affinity for electron-rich F-containing ions compared to the linear polysiloxane, and furthermore has a slightly lower removal rate for F-containing ions in the electrolyte, making the effect of reducing the elution of manganese ions somewhat weaker, and thus is somewhat inferior in improving the cycle performance of the secondary battery.

[0010] In any embodiment of the present application, the linear polysiloxane further comprises a blocking group, and optionally the blocking group comprises at least one selected from the group consisting of polyether, a C1-C8 alkyl group, a C1-C8 halogenated alkyl group, a C1-C8 heteroalkyl group, a C1-C8 halogenated heteroalkyl group, a C2-C8 alkenyl group, a C2-C8 halogenated alkenyl group, a C6-C20 aromatic hydrocarbon group, a C1-C8 alkoxy group, a C2-C8 epoxy group, a hydroxyl group, a C1-C8 hydroxyalkyl group, an amino group, a C1-C8 aminoalkyl group, a carboxyl group, and a C1-C8 carboxyalkyl group.

[0011] In any embodiment of the present application, the linear polysiloxane is selected from the group consisting of polydimethylsiloxane, polydiethylsiloxane, polymethylethylsiloxane, polymethylvinylsiloxane, polyphenylmethylsiloxane, polymethylhydrogensiloxane, carboxyl-functionalized polysiloxane, polymethylchloropropylsiloxane, polymethyltrifluoropropylsiloxane, perfluorooctylmethylpolysiloxane, mercaptopropylpolysiloxane, aminoethylaminopropylpolydimethylsiloxane, methoxy-terminated polydimethylsiloxane, hydroxypropyl-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane, epoxy-terminated polysiloxane, hydroxypropyl-terminated polydimethyl ... and optionally one or more of polydimethylsiloxane, polymethylchloropropylsiloxane, polymethyltrifluoropropylsiloxane, mercaptopropylpolysiloxane, aminoethylaminopropylpolydimethylsiloxane, hydroxydimethylsiloxane, polyether-grafted poly ...

[0012] In any embodiment of the present application, the cyclic polysiloxane includes one or more of cyclic polydimethylsiloxane, cyclic polymethylvinylsiloxane, cyclic polymethylhydrogensiloxane, and cyclic polymethyltrifluoropropylsiloxane, and optionally includes one or more of 1,3,5,7-octamethylcyclotetrasiloxane, 1,3,5,7-tetrahydro-1,3,5,7-tetramethylcyclotetrasiloxane, cyclopentapolydimethylsiloxane, 2,4,6,8-tetramethylcyclotetrasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, hexadecamethyloctasiloxane, and tetradecamethylcycloheptasiloxane.

[0013] In any embodiment of the present application, the number average molecular weight of the organopolysiloxane compound is not more than 300000, and optionally is 400 to 80000. This allows the secondary battery to have both good dynamic performance and high temperature stability.

[0014] In any embodiment of the present application, the mass percentage of the polar functional group in the organopolysiloxane compound is α, where 0≦α<50%, and optionally 5%≦α≦30%, which can better improve the cycle performance and / or high temperature stability of the secondary battery.

[0015] In any embodiment of the present application, the content of the organopolysiloxane compound is 0.01% by weight to 2% by weight, optionally 0.1% by weight to 2% by weight, calculated based on the total weight of the positive electrode material composition, which can better improve the cycle performance and / or high temperature stability of the secondary battery.

[0016] In any embodiment of the present application, the coating amount of the first coating layer is more than 0% by weight and not more than 7% by weight, optionally 4% by weight to 5.6% by weight, calculated based on the weight of the core, so that the coating layer is not too thick and does not affect the dynamic performance of the secondary battery, and the function of the first coating layer can be effectively exerted.

[0017] In any embodiment of the present application, the coating amount of the second coating layer is more than 0% by weight and less than or equal to 6% by weight, optionally 3% by weight to 5% by weight, calculated based on the weight of the core, which can effectively improve the gram capacity (capacity per gram) of the positive electrode active material.

[0018] In any embodiment of the present application, the phosphate of the first coating layer has a lattice spacing of 0.345 nm to 0.358 nm and an included angle of the (111) crystal orientation of 24.25° to 26.45°, which can further improve the cycle performance and rate performance of the secondary battery.

[0019] In any embodiment of the present application, the pyrophosphate of the first coating layer has a lattice spacing of 0.293 nm to 0.326 nm and an included angle of the (111) crystal orientation of 26.41° to 32.57°, which can further improve the cycle performance and rate performance of the secondary battery.

[0020] In any embodiment of the present application, in the core, the ratio of y to 1-y is 1:10 to 10:1, and optionally 1:4 to 1:1, which can further improve the energy density and cycle performance of the secondary battery.

[0021] In any embodiment of the present application, in the core, the ratio of z to 1-z is 1:9 to 1:999, and optionally 1:499 to 1:249, thereby making it possible to further improve the energy density and cycle performance of the secondary battery.

[0022] In any embodiment of the present application, the weight ratio of pyrophosphate to phosphate in the first coating layer is 1:3 to 3:1, and optionally 1:3 to 1:1, which is advantageous for achieving a synergistic effect between pyrophosphate and phosphate.

[0023] In any embodiment of the present application, the crystallinity of the pyrophosphate and the phosphate in the first coating layer is independently 10% to 100%, and optionally 50% to 100%, which is advantageous in that the pyrophosphate can fully exert the effect of reducing the elution of manganese ions and the content of lithium impurities on the surface of the phosphate, and reducing side reactions at the interface.

[0024] In any embodiment of the present application, the above A is at least two selected from Fe, Ti, V, Ni, Co, and Mg, which can further suppress the decrease in surface oxygen activity and the elution of manganese ions.

[0025] In any embodiment of the present application, the positive electrode active material has a Li / Mn antistructure defect concentration of 4% or less, and optionally 2% or less, which can improve the gram capacity and rate performance of the positive electrode active material.

[0026] In any embodiment of the present application, the lattice change rate of the positive electrode active material is 8% or less, and optionally 4% or less, which can improve the rate performance of the secondary battery.

[0027] In any embodiment of the present application, the valence of the surface oxygen of the positive electrode active material is −1.88 or less, and optionally −1.98 to −1.88, which can improve the cycle performance and high-temperature storage performance of the secondary battery.

[0028] In any embodiment of the present application, the compaction ratio per 3 tons of the positive electrode active material is 2.0 g / cm 3 or more, and can be selected to be 2.2g / cm 3This is advantageous for improving the volumetric energy density of the secondary battery.

[0029] In any embodiment of the present application, the positive electrode material composition further includes a conductive agent and an adhesive, and optionally, the content of the adhesive is 1.79% by weight to 10% by weight, calculated based on the total weight of the positive electrode material composition, and optionally, the content of the conductive agent is 0.2% by weight to 10% by weight, calculated based on the total weight of the positive electrode material composition.

[0030] In any embodiment of the present application, the powder resistivity of the positive electrode material composition at 12 MPa is 4Ω / cm to 55Ω / cm, and optionally 4Ω / cm to 40Ω / cm, so that the secondary battery can have better dynamic performance.

[0031] In any embodiment of the present application, the specific surface area of ​​the positive electrode material composition is 8 m 2 / g~20m 2 / g, optionally 8m 2 / g~15m 2 / g, which allows the secondary battery to have better electrochemical performance.

[0032] A second aspect of the present application provides a method for producing a positive electrode material composition, the method including the steps of providing a core material, coating, and mixing.

[0033] In the step of providing a core material, the core is Li 1+x Mn 1-y A y P 1-z R z O 4wherein x is -0.100 to 0.100, and optionally -0.100 to 0.006; y is 0.001 to 0.500, and optionally 0.100 to 0.450; z is 0.001 to 0.100; A is one or more selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and optionally one or more selected from Fe, Ti, V, Ni, Co, and Mg; and R is one or more selected from B, Si, N, and S.

[0034] In the coating process, MP 2 O 7 Powder and XPO containing carbon source 4 providing a suspension of said core material and MP 2 O 7 The powder was mixed with XPO containing a carbon source. 4 and adding the resulting mixture to the suspension, mixing and sintering to obtain a positive electrode active material, wherein the above-mentioned M and X are each independently one or more selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al, and the obtained positive electrode active material has a core-shell structure including the above-mentioned core and a shell covering the above-mentioned core, the shell including a first covering layer covering the above-mentioned core and a second covering layer covering the above-mentioned first covering layer, and the above-mentioned first covering layer is a pyrophosphate MP 2 O 7 and phosphate XPO 4 and the second coating layer comprises carbon.

[0035] In the mixing step, the obtained positive electrode active material is uniformly mixed with an organopolysiloxane compound, an optional adhesive, and an optional conductive agent to obtain a positive electrode material composition.

[0036] In any embodiment of the present application, the step of providing the core material includes the steps of (1) mixing and stirring a manganese source, an element A source and an acid in a container to obtain manganese salt particles doped with element A; and (2) mixing the manganese salt particles doped with element A with a lithium source, a phosphorus source and an element R source in a solvent to obtain a slurry, which is sintered under the protection of an inert gas atmosphere to obtain lithium manganese phosphate doped with element A and element R, wherein the lithium manganese phosphate doped with element A and element R is Li 1+x Mn 1-y A y P 1-z R z O 4 and step (2) in which x is -0.100 to 0.100 and optionally -0.100 to 0.006, y is 0.001 to 0.500 and optionally 0.100 to 0.450, z is 0.001 to 0.100, A is one or more types selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and optionally one or more types of Fe, Ti, V, Ni, Co, and Mg, and R is one or more types selected from B, Si, N, and S.

[0037] In any embodiment of the present application, the above step (1) can be carried out at a temperature of 20°C to 120°C, optionally at a temperature of 25°C to 80°C.

[0038] In any embodiment of the present application, the stirring in step (1) is carried out at 500 rpm to 700 rpm for 60 minutes to 420 minutes, optionally for 120 minutes to 360 minutes.

[0039] By controlling the reaction temperature, stirring speed and mixing time during doping, the doping element can be distributed uniformly, and the crystallinity of the material after sintering can be increased, thereby improving the gram capacity and rate performance of the positive electrode active material.

[0040] In any embodiment of the present application, the source of element A is one or more selected from the group consisting of a simple substance, a sulfate, a halide, a nitrate, an organic acid salt, an oxide, and a hydroxide of element A.

[0041] In any embodiment of the present application, the source of element R is one or more selected from the group consisting of an element R, a sulfate, a halide, a nitrate, an organic acid salt, an oxide or hydroxide, and an inorganic acid of element R.

[0042] By selecting each doping element source within the above range, the performance of the positive electrode active material can be effectively improved.

[0043] In any embodiment of the present application, the MP 2 O 7 The powder is produced by a method in which an element M source and a phosphorus source are added to a solvent to obtain a mixture, the pH of the mixture is adjusted to 4 to 6, the mixture is stirred to sufficiently react, and then dried and sintered, where M is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al.

[0044] In any embodiment of the present application, MP 2 O 7 In the process of producing the powder, the drying step is performed at 100° C. to 300° C., optionally at 150° C. to 200° C., for 4 hours to 8 hours.

[0045] In any embodiment of the present application, MP 2 O 7 In the process of producing the powder, the sintering step is performed at 500° C. to 800° C., and optionally at 650° C. to 800° C., in an inert gas atmosphere for 4 hours to 10 hours.

[0046] In any embodiment of the present application, in the coating step, the sintering temperature for obtaining the positive electrode active material is 500° C. to 800° C., and the sintering time is 4 hours to 10 hours. By controlling the sintering temperature and time for coating, the gram capacity and rate performance of the positive electrode active material can be further improved.

[0047] A third aspect of the present application provides a positive electrode sheet comprising: a positive electrode current collector; and a positive electrode film layer provided on at least one surface of the positive electrode current collector, the positive electrode film layer comprising the positive electrode material composition according to any one of claims 1 to 16 or a positive electrode material composition produced by the method according to any one of claims 17 to 22, and a content of the positive electrode material composition in the positive electrode film layer is 50% by weight or more, calculated based on the total weight of the positive electrode film layer.

[0048] In any embodiment of the present application, the content of the positive electrode material composition in the positive electrode membrane layer is 90% by weight to 100% by weight, calculated based on the total weight of the positive electrode membrane layer.

[0049] In any embodiment of the present application, the solid-liquid contact angle between the positive electrode film layer and the nonaqueous organic solvent is 3° to 90°, optionally 3° to 60°, or further 10° to 30°. When the contact angle is within an appropriate range, the secondary battery can have a high energy density and improved cycle performance, safety performance, and / or rate performance.

[0050] In any embodiment of the present application, the porosity of the positive electrode membrane layer is 15% to 50%, and optionally 15% to 30%. When the porosity is within an appropriate range, the secondary battery can have a high energy density and improved cycle performance, safety performance, and / or rate performance.

[0051] In any embodiment of the present application, the resistance of the positive electrode film layer is greater than 0 and less than or equal to 6Ω, so that the secondary battery has better dynamic performance.

[0052] In any embodiment of the present application, the adhesive strength between the positive electrode film layer and the positive electrode current collector is 0.5 MPa or more, which is advantageous for exhibiting the performance of the secondary battery.

[0053] In any embodiment of the present application, the areal density of the positive electrode film layer is 0.006 g / cm 2 ~0.065g / cm 2 This is advantageous for improving the volumetric energy density of the secondary battery.

[0054] In any embodiment of the present application, the electrolyte absorption rate of the positive electrode membrane layer is 0.0125 μg / s to 100 μg / s, and optionally 0.5 μg / s to 40 μg / s, which is advantageous for improving the electrochemical performance of the secondary battery.

[0055] The positive electrode sheet of the present application can be used in a secondary battery to improve the energy density, cycle performance, safety performance, and / or rate performance of the secondary battery.

[0056] A fourth aspect of the present application provides a secondary battery comprising the positive electrode material composition of the first aspect of the present application, or the positive electrode material composition produced by the method of the second aspect of the present application, or the positive electrode sheet of the third aspect of the present application.

[0057] A fifth aspect of the present application provides a power consuming device including the secondary battery of the fourth aspect of the present application.

[0058] The positive electrode sheet, secondary battery, and power consuming device of the present application contain the positive electrode material composition of the present application and therefore have at least the same advantages as the positive electrode active material composition described above. [Brief description of the drawings]

[0059] In order to more clearly describe the technical solutions of the embodiments of the present application, the drawings necessary for the embodiments of the present application are briefly described below. It is clear that the drawings described below are only some embodiments of the present application. Those skilled in the art can further obtain other drawings based on the drawings even without creative labor. [Figure 1] FIG. 1 is a schematic diagram of an embodiment of a secondary battery of the present application. [Diagram 2] FIG. 2 is an exploded schematic view of the embodiment of the secondary battery of FIG. 1. [Diagram 3] FIG. 1 is a schematic diagram of one embodiment of a battery module of the present application. [Figure 4] FIG. 1 is a schematic diagram of one embodiment of a battery pack of the present application. [Diagram 5] 5 is an exploded schematic view of the embodiment of the battery pack shown in FIG. 4. [Figure 6] 1 is a schematic diagram of an embodiment of a power consuming device powered by a secondary battery according to the present application; [Figure 7] A comparison diagram between the XRD spectrum of the positive electrode active material core prepared in Example 1-1 and the XRD standard spectrum of lithium manganese phosphate (00-033-0804). In the drawings, the drawings are not necessarily drawn to scale. Reference numerals: 1 battery pack, 2 upper case, 3 lower case, 4 battery module, 5 secondary battery, 51 case, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0060] Hereinafter, the positive electrode material composition of the present application, its manufacturing method, and the positive electrode sheet, secondary battery, and power consumption device containing the same will be described in detail with appropriate reference to the drawings that specifically disclose the embodiments. However, unnecessary detailed description may be omitted. For example, detailed description of known matters and duplicated description of substantially the same configuration may be omitted. This is to avoid the following description from becoming unnecessarily redundant and to facilitate understanding by those skilled in the art. Note that the attached drawings and the following description are provided to enable those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0061] The "ranges" disclosed in this application are defined in the form of lower and upper limits, where a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the end values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, when ranges of 60-120 and 80-110 are recited for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also contemplated. Also, when minimum range values ​​1 and 2 and maximum range values ​​3, 4 and 5 are recited, ranges of 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5 may all be contemplated. In this application, unless otherwise stated, the numerical range "a-b" is represented by the abbreviation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" refers to all real numbers between "0-5" throughout this specification, with "0-5" being an abbreviation for combinations of these numerical values. Furthermore, expressing a parameter as an integer greater than or equal to 2 (≧2) is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0062] Unless otherwise specified, all the embodiments and optional embodiments of the present application may be combined with each other to form a new technical solution, and such technical solution is considered to be included in the disclosure content of the present application.

[0063] Unless otherwise stated, all technical features and optional technical features in the present application may be combined with each other to form new technical solutions, and such technical solutions are deemed to be included in the disclosure content of the present application.

[0064] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, but are preferably performed in sequence. For example, the method includes steps (a) and (b) and may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, when it is stated that the method may further include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.

[0065] Unless otherwise specified, the terms "comprise" and "include" used in this application mean open-ended and may also be closed-ended. For example, the terms "comprise" and "include" can mean "comprise" or "include" other components not listed, or "comprise" or "include" only the listed components.

[0066] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any of the following conditions are met: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), or both A and B are true (or exist).

[0067] In this specification, the median diameter Dv50 is the particle diameter corresponding to the material cumulative volume distribution percentage reaching 50%. In this application, the median diameter Dv50 of the material can be measured by laser diffraction particle size analysis. For example, it is measured using a laser particle size analyzer (e.g., Malvern Master Size 3000) with reference to GB / T19077-2016.

[0068] Substituents of compounds are disclosed herein in groups or in ranges, and it is specifically contemplated that such descriptions also include each individual subcombination of the members of these groups and ranges. For example, the term "C1-C8 alkyl" is expressly expected to individually disclose C1, C2, C3, C4, C5, C6, C7, C8, C1-C8, C1-C7, C1-C6, C1-C5, C1-C4, C1-C3, C1-C2, C2-C8, C2-C7, C2-C6, C2-C5, C2-C4, C2-C3, C3-C8, C3-C7, C3-C6, C3-C5, C3-C4, C4-C8, C4-C7, C4-C6, C4-C5, C5-C8, C5-C7, C5-C6, C6-C8, C6-C7, and C7-C8 alkyl groups.

[0069] As used herein, the term "aliphatic hydrocarbon group" includes alkyl groups, alkenyl groups, and alkynyl groups, and the term "heteroaliphatic hydrocarbon group" means an aliphatic hydrocarbon group containing a heteroatom (e.g., N, O, S, etc.). The term "heteroalkyl" means an alkyl group containing a heteroatom (e.g., N, O, S, etc.), and may be, for example, an alkoxy group, an alkylthio group, etc.

[0070] In this specification, the term "coating layer" refers to a material layer coated on the core, and the material layer can completely or partially cover the core. The use of "coating layer" is merely for convenience of description and is not intended to limit the present application. Also, each coating layer can be completely or partially coated.

[0071] As used herein, the term "source" refers to a compound from which an element is derived, and by way of example, types of "source" include, but are not limited to, carbonates, sulfates, nitrates, elements, halides, oxides, and hydroxides.

[0072] As used herein, the terms "plurality" and "multiple types" mean two or more than two.

[0073] In this specification, a certain numerical value referred to as "about" indicates a range, indicating a range of ±10% of the said numerical value.

[0074] As discovered through the actual work of the inventors of the present application, lithium manganese phosphate LiMnPO 4 In the case of the positive electrode active material, manganese ion dissolution is serious during the charge and discharge process with a deep charge and discharge depth. In the prior art, there is an attempt to reduce side reactions at the interface by coating lithium manganese phosphate with lithium iron phosphate, but such a coating cannot prevent the migration of the dissolved manganese ions into the electrolyte. The dissolved manganese ions are reduced to metallic manganese after migrating to the negative electrode. These generated metallic manganese correspond to a "catalyst" and can catalyze the decomposition of the SEI film (solid electrolyte interphase) on the surface of the negative electrode. Some of the generated by-products are gases, which make the battery prone to expansion and affect the safety performance of the secondary battery, and the other part is deposited on the surface of the negative electrode, which inhibits the channel of lithium ions to the negative electrode, leading to an increase in the resistance of the secondary battery and affecting the dynamic performance of the secondary battery. In addition, the electrolyte and active lithium ions inside the battery are constantly consumed to replenish the lost SEI film, which also has an irreversible effect on the capacity retention rate of the secondary battery.

[0075] After extensive research, the inventors have found that the problems of manganese ion elution and high surface reaction activity in the positive electrode active material of lithium manganese phosphate are solved by the Mn 3+ Jahn-Teller effect and Li + It was found that this may be due to a change in the size of the channel. Therefore, the inventors modified lithium manganese phosphate to significantly reduce the elution of manganese ions and the lattice change rate, and obtained a positive electrode active material with better cycle performance, safety performance, and / or rate performance. At the same time, the inventors of the present application found that the use of a positive electrode active material in combination with an organopolysiloxane compound reduces the erosion of the electrolyte on the surface of the positive electrode active material, which is advantageous for fully exhibiting the electrochemical performance of the positive electrode active material. Positive electrode material composition

[0076] Specifically, a first aspect of the present application provides a positive electrode material composition including a positive electrode active material having a core-shell structure and an organopolysiloxane compound.

[0077] The positive electrode active material includes a core and a shell that covers the core. The core is Li 1+x Mn 1-y A y P 1-z R z O 4 wherein x is −0.100 to 0.100, y is 0.001 to 0.500, and z is 0.001 to 0.100; A is one or more selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and optionally is one or more of Fe, Ti, V, Ni, Co, and Mg; R is one or more selected from B, Si, N, and S; the shell includes a first coating layer coating the core and a second coating layer coating the first coating layer, and the first coating layer is a pyrophosphate MP 2 O 7 and phosphate XPO 4 wherein M and X are each independently one or more selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and the second coating layer contains carbon.

[0078] Unless otherwise specified, in the above chemical formula, when A is two or more elements, the above-mentioned limit on the numerical range of y is not only limited to the stoichiometric number of each element that becomes A, but also limited to the sum of the stoichiometric numbers of each element that becomes A. For example, when A is two or more elements A1, A2, ..., An, the stoichiometric numbers y1, y2, ..., yn of A1, A2, ..., An must be within the numerical range limited by y in this application, and the sum of y1, y2, ..., yn must also be within this numerical range. Similarly, when R is two or more elements, limiting the numerical range of the stoichiometric number of R in this application has the above meaning.

[0079] The lithium manganese phosphate positive electrode active material of the present application has a core-shell structure with two coating layers. The core is Li 1+x Mn 1-y A y P 1-z R z O 4 The above core includes: Element A doped into the manganese site of lithium manganese phosphate contributes to the reduction of the lattice change rate of lithium manganese phosphate in the lithium insertion and desorption process, improves the structural stability of the positive electrode active material of lithium manganese phosphate, greatly reduces the dissolution of manganese ions, and reduces the oxygen activity of the particle surface; Element R doped into the phosphorus site changes the difficulty of changing the Mn-O bond distance, lowers the lithium ion migration barrier, promotes the migration of lithium ions, and improves the rate performance of secondary batteries.

[0080] The first coating layer of the positive electrode active material of the present application includes pyrophosphate and phosphate. The transition metal pyrophosphate has a high migration barrier (>1 eV), so it can effectively suppress the elution of transition metal ions. In addition, phosphate has excellent lithium ion transport ability and can reduce the content of lithium impurities on the surface.

[0081] The second coating layer of the positive electrode active material of the present application is a carbon-containing layer, and is therefore LiMnPO 4The conductive performance and desolvation ability of the positive electrode active material can be effectively improved. In addition, the "barrier" action of the second coating layer further inhibits the migration of manganese ions into the electrolyte, thereby reducing the corrosion of the electrolyte against the positive electrode active material.

[0082] Therefore, the present application provides a method for doping lithium manganese phosphate with a specific element to coat the surface thereof, thereby effectively suppressing the elution of manganese ions during the lithium insertion / extraction process while promoting the movement of lithium ions, thereby improving the cycle performance, safety performance, and / or rate performance of the secondary battery.

[0083] The positive electrode material composition of the present application includes a positive electrode active material and an organopolysiloxane compound. The inventors of the present application have found that the use of the positive electrode active material and the organopolysiloxane compound in combination can alleviate the erosion of the electrolyte on the surface of the positive electrode active material, reduce the elution of manganese ions, and is advantageous in improving the electrochemical performance of the positive electrode active material. Possible causes include the Si-O skeleton of the organopolysiloxane compound being able to remove ions containing F in the electrolyte, thereby reducing the acidity of the electrolyte and alleviating the erosion of the acidic substances in the electrolyte on the surface of the positive electrode active material; and the organopolysiloxane compound has a certain water repellency, which, after producing a positive electrode sheet together with the positive electrode active material, increases the contact angle between the obtained positive electrode sheet and the electrolyte, thereby alleviating the erosion of the electrolyte on the surface of the positive electrode active material.

[0084] Therefore, a power consuming device such as a positive electrode sheet and a secondary battery using the positive electrode material composition of the present application can combine high energy density with improved cycle performance, safety performance, and / or rate performance.

[0085] The positive electrode active material core of the present application is LiMnPO 4 It is almost consistent with the position of the main characteristic peak before doping, and the positive electrode active material core of the doped lithium manganese phosphate of the present application is free of impurity phase, and the secondary battery performance is improved mainly by the doping of elements, not by the impurity phase.

[0086] In some embodiments, the coating amount of the first coating layer is optionally greater than 0% and not more than 7% by weight, and optionally 4% to 5.6% by weight, based on the weight of the core. When the coating amount of the first coating layer is within the above range, the transport of lithium ions can be further promoted while further suppressing the elution of manganese ions. In addition, the following situation can be effectively avoided. If the coating amount of the first coating layer is too small, the effect of suppressing the elution of pyrophosphate on manganese ions may be insufficient, and the improvement of the transport performance of lithium ions may not be significant. Also, if the coating amount of the first coating layer is too large, the coating layer may be too thick, increasing the resistance of the battery, and affecting the dynamic performance of the secondary battery.

[0087] In some embodiments, optionally, the coating amount of the second coating layer is more than 0% and not more than 6% by weight based on the weight of the core, and optionally 3% to 5% by weight. As a carbon-containing layer of the second coating layer, it exerts a "barrier" function, avoids direct contact between the positive electrode active material and the electrolyte, reduces the erosion of the electrolyte to the positive electrode active material, and can improve the safety performance of the secondary battery at high temperatures. On the other hand, it has a strong conductive ability, which can reduce the internal resistance of the battery and improve the dynamic performance of the secondary battery. However, because the gram capacity of the carbon material is low, if the amount of the second coating layer is too large, the gram capacity of the entire positive electrode active material may be reduced. Therefore, if the coating amount of the second coating layer is in the above range, the dynamic performance and safety performance of the secondary battery can be further improved without impairing the gram capacity of the positive electrode active material.

[0088] In the above core, x is -0.100 to 0.100, for example, x may be 0.006, 0.004, 0.003, 0.002, 0.001, 0, -0.001, -0.003, -0.004, -0.005, -0.006, -0.007, -0.008, -0.009, -0.100. Optionally, x is -0.100 to 0.006.

[0089] In the above core, y is 0.001 to 0.500, for example, y may be 0.100, 0.200, 0.250, 0.300, 0.350, 0.400, 0.450. Optionally, y is 0.100 to 0.450.

[0090] In the core, z is 0.001 to 0.100, and may be, for example, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, or 0.100.

[0091] In some embodiments, optionally in the core, the ratio of y to 1-y is 1:10 to 10:1, optionally 1:4 to 1:1, where y represents the sum of the stoichiometric numbers of the doping elements at the Mn site. If the above condition is satisfied, the energy density and cycle performance of the secondary battery can be further improved.

[0092] In some embodiments, optionally in the core, the ratio of z to 1-z is 1:9 to 1:999, optionally 1:499 to 1:249, where y represents the sum of the stoichiometric numbers of the doping elements at the P site. If the above condition is satisfied, the energy density and cycle performance of the secondary battery can be further improved.

[0093] In some embodiments, optionally, A is at least two selected from Fe, Ti, V, Ni, Co, and Mg.

[0094] Doping two or more of the above elements simultaneously into the manganese site of the lithium manganese phosphate positive electrode active material is advantageous in improving the doping effect, suppressing the dissolution of manganese ions to reduce the lattice change rate, and reducing the consumption of the electrolyte and active lithium ions, while further reducing the activity of surface oxygen and reducing side reactions at the interface between the positive electrode active material and the electrolyte, which is advantageous in improving the cycle performance and high-temperature storage performance of the secondary battery.

[0095] In some embodiments, optionally, the phosphate of the first coating layer has a lattice spacing of 0.345 nm to 0.358 nm and an included angle of the (111) crystal orientation of 24.25° to 26.45°.

[0096] In some embodiments, optionally, the interplanar spacing of the pyrophosphate of the first coating layer is 0.293 nm to 0.326 nm, and the included angle of the (111) crystal orientation is 26.41° to 32.57°.

[0097] When the included angle between the interplanar spacing of the phosphate and pyrophosphate in the first coating layer and the crystal orientation (111) is within the above range, impurity phases in the coating layer can be effectively avoided, and the gram capacity, cycle performance, and rate performance of the positive electrode active material can be improved.

[0098] In some embodiments, the weight ratio of pyrophosphate to phosphate in the first coating layer is optionally 1:3 to 3:1. The weight ratio of pyrophosphate to phosphate in the first coating layer is optionally 1:3 to 1:1. The appropriate compounding ratio of pyrophosphate and phosphate is advantageous in fully exerting the synergistic effect of the two, and can effectively inhibit the elution of manganese ions while effectively reducing the impurity lithium content on the surface and reducing side reactions at the interface. In addition, if there is too much pyrophosphate and too little phosphate, the resistance of the battery may increase, and if there is too much phosphate and too little pyrophosphate, the effect of suppressing the elution of manganese ions is not significant, which can be effectively avoided.

[0099] In some embodiments, optionally, the crystallinity of the pyrophosphate and the phosphate in the first coating layer is independently 10% to 100%. Alternatively, the crystallinity of the pyrophosphate and the phosphate in the first coating layer is independently 50% to 100%. In the first coating layer of the lithium manganese phosphate positive electrode active material of the present application, the pyrophosphate and the phosphate having a certain degree of crystallinity are advantageous in stabilizing the structure of the first coating layer and reducing lattice defects. This is advantageous in that the pyrophosphate fully exerts the effect of inhibiting the dissolution of manganese ions, while the phosphate is advantageous in reducing the content of lithium impurities on the surface and reducing the valence of surface oxygen, thereby reducing side reactions at the interface between the positive electrode active material and the electrolyte, reducing consumption to the electrolyte, and improving the cycle performance and safety performance of the secondary battery.

[0100] In the present application, the crystallinity of pyrophosphates and phosphates can be adjusted by adjusting process conditions during the sintering process, such as the sintering temperature, sintering time, etc. The crystallinity of pyrophosphates and phosphates can be measured by methods well known in the art, such as X-ray diffraction, density method, infrared spectroscopy, differential scanning calorimetry, and nuclear magnetic resonance spectroscopy.

[0101] In some embodiments, the positive electrode active material optionally has a Li / Mn anti-structure defect concentration of 4% or less, optionally 2% or less. Li / Mn anti-structure defects are LiMnPO 4 In the crystal lattice, Li + and Mn 2+ The Li / Mn anti-structure defect concentration means that the Mn 2+ Replaced by Li + But Li + Li is the percentage of the total amount of + The transport channel is a one-dimensional channel, and Mn 2+ Li + Since the transition is difficult in the transport channel, the anti-structural defect Mn 2+ Li +In the positive electrode active material of the present application, the gram capacity and rate performance of the positive electrode active material can be improved by limiting the Li / Mn antistructural defect concentration to a low level. In the present application, the antistructural defect concentration can be measured, for example, in accordance with JIS K 0131-1996.

[0102] In some embodiments, optionally, the lattice change rate of the positive electrode active material is 8% or less, optionally 6% or less, and further optionally 4% or less. LiMnPO 4 The lithium insertion and desorption process is a two-phase reaction. The interfacial stress between the two phases is determined by the magnitude of the lattice change rate. The smaller the lattice change rate, the smaller the interfacial stress. + Therefore, reducing the lattice change rate of the core is + This is advantageous in improving the transport capacity of the secondary battery, thereby improving the rate performance of the secondary battery.

[0103] In some embodiments, optionally, the average discharge voltage of the coil cell of the positive electrode active material is 3.5 V or more and the discharge gram capacity is 140 mAh / g or more, and optionally, the average discharge voltage is 3.6 V or more and the discharge gram capacity is 145 mAh / g or more. 4 Although the average discharge voltage of is more than 4.0V, its discharge gram capacity is low, usually less than 120mAh / g, so the energy density of the secondary battery is low. By adjusting the lattice change rate through doping, its discharge gram capacity can be greatly improved, and when the average discharge voltage is slightly reduced, the energy density of the entire secondary battery is obviously increased.

[0104] In some embodiments, optionally, the valence of the surface oxygen of the positive electrode active material is -1.88 or less, optionally -1.98 to -1.88. This is because the higher the valence of oxygen in the compound, the stronger the ability to obtain electrons, i.e., the stronger the oxidizing property. In the lithium manganese phosphate positive electrode active material of the present application, by controlling the surface valence of oxygen to a low level, the reaction activity of the surface of the positive electrode active material can be reduced, and the side reaction at the interface between the positive electrode active material and the electrolyte can be reduced, thereby improving the cycle performance and high-temperature storage performance of the secondary battery.

[0105] In some embodiments, optionally, the positive electrode active material has a compaction density of 2.0 g / cm at 3 ton (T). 3 or more, optionally 2.2 g / cm 3 That is all. The higher the compaction degree of the positive electrode active material, i.e., the larger the weight of the active material per volume, the more advantageous it is for improving the volumetric energy density of the secondary battery. In this application, the compaction degree can be measured, for example, in accordance with GB / T 24533-2009.

[0106] In some embodiments, the organopolysiloxane compound comprises at least one structural unit shown in Formula 1.

number

[0107] These functional groups can complex manganese ions and / or react with acidic substances in the electrolyte, thereby reducing the elution of manganese ions and further improving the cycle performance and / or high temperature stability of the secondary battery.

[0108] When these functional groups have electron-withdrawing properties, they can make the Si in the Si-O skeleton of the organopolysiloxane compound more electron-deficient, thereby further strengthening the affinity with ions containing F in the electrolyte, further mitigating the erosion of acidic substances on the surface of the positive electrode active material in the electrolyte, reducing the elution of manganese ions, and significantly improving the cycle performance and / or high-temperature stability of the secondary battery.

[0109] In some embodiments, the organopolysiloxane compound includes one or more selected from a polysiloxane having a linear structure and a polysiloxane having a cyclic structure, and optionally the organopolysiloxane compound is selected from a polysiloxane having a linear structure.

[0110] This further alleviates the corrosion of the surface of the positive electrode active material by the acidic substance in the electrolyte and reduces the elution of manganese ions, thereby significantly improving the cycle performance and storage performance of the secondary battery. Since the electrons in the ring of the cyclic polysiloxane have a certain degree of delocalization, the Si-O skeleton of the cyclic polysiloxane has a low affinity for electron-rich F-containing ions compared to the linear polysiloxane, and furthermore, the removal rate of F-containing ions in the electrolyte is somewhat low, so the effect of reducing the elution of manganese ions is somewhat weak, and the effect of improving the cycle performance of the secondary battery is somewhat inferior.

[0111] In some embodiments, the linear polysiloxane may further include a blocking group. Optionally, the blocking group includes at least one selected from the group consisting of polyether, C1-C8 alkyl group, C1-C8 halogenated alkyl group, C1-C8 heteroalkyl group, C1-C8 halogenated heteroalkyl group, C2-C8 alkenyl group, C2-C8 halogenated alkenyl group, C6-C20 aromatic hydrocarbon group, C1-C8 alkoxy group, C2-C8 epoxy group, hydroxyl group, C1-C8 hydroxyalkyl group, amino group, C1-C8 aminoalkyl group, carboxyl group, and C1-C8 carboxyalkyl group.

[0112] In some embodiments, the molecular formula of the cyclic polysiloxane can be represented as Formula 2, where n represents the degree of polymerization of the structural unit represented in Formula 1. Optionally, n≦12, n≦11, n≦10, n≦9, or n≦8.

number

[0113] Examples of the linear polysiloxane include polydimethylsiloxane, polydiethylsiloxane, polymethylethylsiloxane, polymethylvinylsiloxane, polyphenylmethylsiloxane, polymethylhydrogensiloxane, carboxyl-functionalized polysiloxane, polymethylchloropropylsiloxane, polymethyltrifluoropropylsiloxane, perfluorooctylmethylpolysiloxane, mercaptopropylpolysiloxane, aminoethylaminopropylpolydimethylsiloxane, methoxy-terminated polydimethylsiloxane, and the like. The linear polysiloxane may include, but is not limited to, one or more of the following: polydimethylsiloxane, hydroxypropyl-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane, epoxy-terminated polysiloxane, hydroxy-terminated polydimethylsiloxane, polyether-terminated polydimethylsiloxane, side chain aminopropyl polysiloxane, side chain hydroxylmethyl polysiloxane, side chain hydroxylpropyl polysiloxane, side chain polyether-grafted polydimethylsiloxane, side chain phosphate ester-grafted polydimethylsiloxane. Optionally, the linear polysiloxane may include one or more of the following: polydimethylsiloxane, polymethylchloropropyl siloxane, polymethyltrifluoropropyl siloxane, mercaptopropyl polysiloxane, aminoethylaminopropyl polydimethylsiloxane, hydroxy-terminated dimethylsiloxane, polyether-terminated polydimethylsiloxane, side chain phosphate ester-grafted polydimethylsiloxane.

[0114] For example, the polysiloxane of the cyclic structure may include, but is not limited to, one or more of cyclic polydimethylsiloxane, cyclic polymethylvinylsiloxane, cyclic polymethylhydrogensiloxane, and cyclic polymethyltrifluoropropylsiloxane. Optionally, the polysiloxane of the cyclic structure may include one or more of 1,3,5,7-octamethylcyclotetrasiloxane, 1,3,5,7-tetrahydro-1,3,5,7-tetramethylcyclotetrasiloxane, cyclopentapolydimethylsiloxane, 2,4,6,8-tetramethylcyclotetrasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, hexadecamethyloctasiloxane, and tetradecamethylcycloheptasiloxane.

[0115] In some embodiments, the number average molecular weight of the organopolysiloxane compound is 300000 or less, and may be, for example, 400-300000, 400-200000, 400-100000, 400-80000, 400-50000, 400-20000, 400-10000, 1000-100000, 1000-50000, 1000-20000, or 1000-10000. The number average molecular weight of the organopolysiloxane compound can be measured by a method well known in the art, for example, gel permeation chromatography (GPC). The measuring instrument can be a PL-GPC220 high temperature gel permeation chromatography. In the present application, the "organopolysiloxane compound" may be an oligomer or a polymer.

[0116] When the number average molecular weight of organopolysiloxane compound is within a suitable range, the secondary battery can have both good dynamic performance and high temperature stability.In addition, when the number average molecular weight of organopolysiloxane compound is too small, its hydrophobicity may be poor, so that the contact angle between the positive electrode film layer and the electrolyte cannot be effectively increased, and the erosion of the electrolyte on the surface of the positive electrode active material cannot be effectively alleviated, so that the improvement effect of the cycle performance and / or high temperature stability of the secondary battery may not be significant.In addition, when the number average molecular weight of organopolysiloxane compound is too large, its hydrophobicity may be strong, and at the same time, it is also disadvantageous to the dispersion of slurry, which affects the improvement effect of the performance of the secondary battery.

[0117] In some embodiments, the weight percentage of polar functional groups in the organopolysiloxane compound is α, where 0≦α<50%, optionally 5%≦α≦30%.

[0118] In the present application, the "mass percentage of polar functional groups in the organopolysiloxane compound" refers to the mass percentage of R 1 , R 2 and the mass ratio of the polar functional group in the blocking group. In this application, the polar functional group is -COOH, -OH, -SH, -CN, -SCN, an amino group (-NH 2 , -NH-), phosphate ester group, carboxylate group (-COO-), amide group (-CONH-), aldehyde group (-CHO), sulfonyl group (-S(=O) 2 -), polyether segment, halogen atom, alkoxy group, and epoxy group. When the polar functional group is directly bonded to the silicon atom, α represents the mass fraction of these polar functional groups in the organopolysiloxane compound. When the polar functional group is not directly bonded to the silicon atom, α represents the mass fraction of the polar functional group and a divalent to tetravalent methyl group (e.g., -CH 2In this case, the "divalent to tetravalent methyl group" represents the sum of the mass fractions of the -CF-, -CH-, -C-, etc. in the organopolysiloxane compound, where the "divalent to tetravalent methyl group" represents the carbon atom directly bonded to the polar functional group and located between the polar functional group and the silicon atom, and other non-polar functional groups bonded to the carbon atom. Taking polymethyltrifluoropropylsiloxane as an example, α represents the sum of the mass fractions of the -CF 3 This does not include the ethylene group. For example, in the case of polymethylchloropropylsiloxane, α is -CH 2 This refers to the mass percentage of Cl, not including the ethylene group. For example, in the case of hydroxypropyl-terminated polydimethylsiloxane, α is -CH 2 The mass percentage of the polar functional group in the organopolysiloxane compound can be measured by a method well known in the art, for example, a titration method (e.g., acid-alkali titration method, oxidation-reduction titration method, precipitation titration method), infrared spectroscopy, or nuclear magnetic resonance spectroscopy.

[0119] When the content of polar functional groups in the organopolysiloxane compound is within an appropriate range, the effect of reducing the acidity of the electrolyte and removing ions containing F in the electrolyte is better, which can better mitigate the erosion of the acidic substances in the electrolyte on the surface of the positive electrode active material, and can better improve the cycle performance and / or high temperature stability of the secondary battery. In addition, when the content of polar functional groups in the organopolysiloxane compound is too high, the effect of reducing the acidity of the electrolyte and removing ions containing F in the electrolyte is not further improved, but the contact angle between the positive electrode film layer and the electrolyte may be small, which can effectively avoid the situation where the effect of improving the cycle performance of the secondary battery is not significant.

[0120] In some embodiments, the content of the organopolysiloxane compound is 0.01% by weight to 2% by weight, optionally 0.1% by weight to 2% by weight, based on the total weight of the positive electrode material composition. When the content of the organopolysiloxane compound is within an appropriate range, the effect of reducing the acidity of the electrolyte and removing ions containing F in the electrolyte can be better, which can better mitigate the erosion of the acidic substances in the electrolyte on the surface of the positive electrode active material, and better improve the cycle performance and / or high temperature stability of the secondary battery. In addition, if the content of the organopolysiloxane compound is too high, it may affect the wettability of the positive electrode film layer to the electrolyte, which may affect the dynamic performance of the secondary battery. In addition, if the content of the organopolysiloxane compound is too high, the energy density of the secondary battery will be reduced because the organopolysiloxane compound does not provide capacity. If the content of the organopolysiloxane compound is too low, the acidity of the electrolyte will be reduced, and the effect of removing F-containing ions in the electrolyte will be insignificant, and the erosion of the acidic substances in the electrolyte on the surface of the positive electrode active material will not be effectively alleviated, so that the effect of improving the cycle performance and / or high temperature stability of the secondary battery will be insignificant.

[0121] In some embodiments, the positive electrode material composition may further include an adhesive. The adhesive may be a material known in the art that exhibits an adhesive effect. Optionally, the adhesive includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin. Optionally, the content of the adhesive is 1.79% to 10% by weight, and optionally 2% to 5% by weight, calculated based on the total weight of the positive electrode material composition.

[0122] In some embodiments, the positive electrode material composition may further include a conductive agent. The conductive agent may be a substance known in the art that has an electronic conductive effect. Optionally, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon particles, carbon nanotubes, graphene, and carbon nanofibers. Optionally, the content of the conductive agent is 0.2% to 10% by weight, optionally 0.5% to 5% by weight, calculated based on the total weight of the positive electrode material composition.

[0123] In some embodiments, the powder resistivity of the positive electrode material composition at 12 MPa is 4Ω / cm to 55Ω / cm, and optionally 4Ω / cm to 50Ω / cm. By adjusting the powder resistivity of the positive electrode material composition to a suitable range, the dynamic performance of the secondary battery can be improved. The powder resistivity of the positive electrode material composition can be measured by a method known in the art. For example, it can be tested using a powder resistivity meter with reference to GB / T 30835-2014. One exemplary test method includes weighing a specified amount of powder of a sample to be measured and placing it in a special mold, and setting a test pressure to obtain powder resistivities under different pressures. In the present application, the test pressure can be set to 12Mpa. The measurement instrument can be a Suzhou Jingge ST2722-SZ type four-probe powder resistivity meter.

[0124] In some embodiments, the specific surface area of ​​the positive electrode material composition is 8 m 2 / g~20m 2 / g, optionally 8m 2 / g~15m 2 / g. By adjusting the specific surface area of ​​the positive electrode material composition to an appropriate range, it is possible to reduce side reactions at the interface between the positive electrode sheet using the composition and the electrolyte, and reduce the volume expansion of the secondary battery. This allows the secondary battery to have better electrochemical performance. The specific surface area of ​​the positive electrode material composition can be measured by a method known in the art. For example, it can be tested by the nitrogen gas adsorption specific surface area analysis test method with reference to GB / T 19587-2017, and calculated by the BET (Brunauer Emmett Teller) method. The nitrogen gas adsorption specific surface area analysis test can be performed using a Tri-Star 3020 type specific surface area pore size analysis tester from Micromeritics, USA. Manufacturing method

[0125] A second aspect of the present application provides a method for producing a positive electrode material composition according to the first aspect of the present application, comprising the steps of providing a core material, coating and mixing.

[0126] In the step of providing a core material, the core is Li 1+x Mn 1-y A y P 1-z R z O 4 wherein x is -0.100 to 0.100, and optionally -0.100 to 0.006; y is 0.001 to 0.500, and optionally 0.100 to 0.450; z is 0.001 to 0.100; A is one or more selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and optionally one or more selected from Fe, Ti, V, Ni, Co, and Mg; and R is one or more selected from B, Si, N, and S.

[0127] In the coating process, MP 2 O 7 Powder and carbon-containing source XPO 4 providing a suspension of said core material, MP 2 O7 Powder containing carbon source XPO 4 and adding the resulting mixture to the suspension, mixing and sintering to obtain a positive electrode active material, wherein the above M and X are each independently one or more selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al, and the obtained positive electrode active material has a core-shell structure and includes the above core and a shell covering the above core, the shell includes a first covering layer covering the above core and a second covering layer covering the above first covering layer, and the above first covering layer is a pyrophosphate MP 2 O 7 and phosphate XPO 4 and the second coating layer comprises carbon.

[0128] In the mixing step, the obtained positive electrode active material is uniformly mixed with an organopolysiloxane compound, an optional adhesive, and an optional conductive agent to obtain a positive electrode material composition.

[0129] The manufacturing method of the present application is not particularly limited in terms of the origin of the material. Optionally, the core material in the manufacturing method of the present application may be commercially available or may be manufactured by the method of the present application. Optionally, the core material is manufactured by the following method:

[0130] In some embodiments, optionally, the step of providing the core material includes the following steps (1) and (2): In step (1), a manganese source, an element A source, and an acid are mixed and stirred in a container to obtain manganese salt particles doped with element A; In step (2), the manganese salt particles doped with element A are mixed with a lithium source, a phosphorus source, and an element R source in a solvent to obtain a slurry, which is sintered under the protection of an inert gas atmosphere to obtain lithium manganese phosphate doped with element A and element R, where the lithium manganese phosphate doped with element A and element R is Li 1+x Mn 1-y A y P 1-z R z O 4wherein x is −0.100 to 0.100 and optionally −0.100 to 0.006, y is 0.001 to 0.500 and optionally 0.100 to 0.450, z is 0.001 to 0.100, A is one or more types selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and optionally one or more types selected from Fe, Ti, V, Ni, Co, and Mg, and R is one or more types selected from B, Si, N, and S.

[0131] In some embodiments, optionally, step (1) can be carried out at a temperature of 20°C to 120°C, and optionally at a temperature of 25°C to 80°C.

[0132] In some embodiments, the stirring in step (1) is carried out at 500 rpm to 700 rpm for 60 minutes to 420 minutes, optionally for 120 minutes to 360 minutes.

[0133] By controlling the reaction temperature, stirring speed and mixing time during doping, the doping element can be uniformly distributed, lattice defects can be reduced, the elution of manganese ions can be suppressed, side reactions at the interface between the positive electrode active material and the electrolyte can be reduced, and the gram capacity and rate performance of the positive electrode active material can be improved.

[0134] In the present application, an element source may include one or more of the following: an element, a sulfate, a halide, a nitrate, an organic acid salt, an oxide, or a hydroxide of the element. On that premise, the source can realize the manufacturing method of the present application. For example, the element A source is one or more selected from the element A, a sulfate, a halide, a nitrate, an organic acid salt, an oxide, or a hydroxide, and / or the element R source is one or more selected from the element R, a sulfate, a halide, a nitrate, an organic acid salt, an oxide, or a hydroxide, and an inorganic acid of the element R.

[0135] Optionally, in some embodiments, the manganese source in the present application is one or more selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, and manganese carbonate.

[0136] In some embodiments, optionally, element A is iron, and optionally, the source of iron is one or more selected from ferrous carbonate, ferrous hydroxide, and ferrous sulfate.

[0137] In some embodiments, optionally in step (1), the acid is one or more selected from an organic acid such as oxalic acid, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, and optionally oxalic acid. In some embodiments, the acid is a dilute acid having a concentration of 60% by weight or less.

[0138] In some embodiments, optionally, the inorganic acid of element R is one or more selected from phosphoric acid, nitric acid, boric acid, silicic acid, orthosilicic acid.

[0139] In some embodiments, optionally, the lithium source in the present application is one or more selected from lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate.

[0140] In some embodiments, optionally, the phosphorus source in the present application is one or more selected from the group consisting of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, and phosphoric acid.

[0141] Optionally, in some embodiments, the carbon source in the present application is an organic carbon source, and the organic carbon source is one or more selected from starch, sucrose, glucose, polyvinyl alcohol, polyethylene glycol, and citric acid.

[0142] In some embodiments, optionally, the solvent used in the manufacturing method of the present application is a solvent commonly used in the art. For example, the solvent in the manufacturing method of the present application may be at least one selected from ethanol and water (e.g., deionized water) independently.

[0143] In some embodiments, the pH of the solution is selectively controlled to 4 to 6 during the process of producing manganese salt particles doped with the A element. In this application, the pH of the mixture obtained can be adjusted by a method commonly used in the art. For example, it can be obtained by adding an acid or an alkali.

[0144] In some embodiments, optionally, in step (2), the molar ratio of the manganese salt particles doped with element A to the lithium source and the phosphorus source is 1:(0.5-2.1):(0.5-2.1).

[0145] In some embodiments, optionally, in step (2), the sintering conditions are sintering in an inert gas atmosphere or a mixed atmosphere of an inert gas and hydrogen gas at 600° C. to 800° C. for 4 hours to 10 hours, which increases the crystallinity of the material after sintering and can improve the gram capacity and rate performance of the positive electrode active material.

[0146] In some embodiments, optionally, the mixture of inert gas and hydrogen gas is nitrogen gas (70% to 90% by volume) + hydrogen gas (10% to 30% by volume).

[0147] In some embodiments, optionally, the MP 2 O 7 The powder is a commercially available product. Alternatively, the above MP 2 O 7The powder is obtained by adding an element M source and a phosphorus source to a solvent to obtain a mixture, adjusting the pH of the mixture to 4 to 6, stirring to sufficiently react, and then drying and sintering, where M is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al.

[0148] In some embodiments, optionally, MP 2 O 7 In the powder manufacturing process, the drying step is performed at 100° C. to 300° C., optionally at 150° C. to 200° C., for 4 hours to 8 hours.

[0149] In some embodiments, optionally, MP 2 O 7 In the powder manufacturing process, the sintering step is performed at 500° C. to 800° C., and optionally at 650° C. to 800° C., in an inert gas atmosphere for 4 to 10 hours.

[0150] In some embodiments, optionally, the carbon source is 4 The suspension is commercially available. Alternatively, it can be prepared by homogeneously mixing a lithium source, an X source, a phosphorus source, and a carbon source in a solvent, followed by heating the reaction mixture to 60° C. to 120° C. and maintaining it for 2 to 8 hours to obtain XPO containing a carbon source. 4 Optionally, the suspension is prepared by obtaining a suspension of XPO containing a carbon source. 4 In the process of preparing the suspension, the pH of the mixture is adjusted to 4-6.

[0151] In some embodiments, the lithium manganese phosphate (core), MP, optionally doped with the A and R elements, may be coated in the coating step. 2 O 7 XPO of powder and carbon-containing sources 4 The mass ratio of the suspension is 1:(0.001-0.05):(0.001-0.05).

[0152] In some embodiments, optionally, the sintering temperature when obtaining the positive electrode active material in the coating step is 500° C. to 800° C., and the sintering time is 4 hours to 10 hours.

[0153] In some embodiments, optionally, the median diameter Dv50 of the primary particles of the bilayer-coated lithium manganese phosphate positive electrode active material of the present application is 50 nm to 2000 nm. Positive electrode sheet

[0154] A third aspect of the present application provides a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector, the positive electrode film layer comprising the positive electrode material composition of the first aspect of the present application or the positive electrode material composition produced by the method of the second aspect of the present application, and the content of the positive electrode material composition in the positive electrode film layer is 50% by weight or more, calculated based on the total weight of the positive electrode film layer. The positive electrode current collector has two surfaces facing each other in a thickness direction, and the positive electrode film layer is provided on the two facing surfaces of the positive electrode current collector.

[0155] In some embodiments, optionally, the content of the positive electrode material composition in the positive electrode membrane layer is 90% by weight to 100% by weight, calculated based on the total weight of the positive electrode membrane layer.

[0156] The positive electrode membrane layer does not exclude other components than the positive electrode material composition of the first aspect of the present application or the positive electrode material composition produced by the method of the second aspect of the present application. For example, the positive electrode membrane layer may further include other positive electrode active materials other than the bilayer-coated lithium manganese phosphate positive electrode active material of the present application. Optionally, the other positive electrode active materials may include at least one of lithium transition metal oxides and their modifying compounds. For example, the other positive electrode active materials may include at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modifying compounds.

[0157] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. An example of the metal foil may be an aluminum foil. The composite current collector may include a polymeric material base layer and a metal material layer formed on at least one surface of the polymeric material base layer. For example, the metal material may be at least one selected from aluminum, an aluminum alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. For example, the polymeric material base layer may be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), and the like.

[0158] In some embodiments, the solid-liquid contact angle between the positive electrode film layer and the non-aqueous organic solvent is 3° to 90°, optionally 3° to 60°, or even 10° to 30°. When the contact angle is within a suitable range, the secondary battery can have both high energy density and improved cycle performance, safety performance, and / or rate performance. In addition, if the contact angle is too small, the erosion of the acidic substance in the electrolyte on the surface of the positive electrode active material cannot be effectively alleviated, and the effect of improving the cycle performance may not be significant, and if the contact angle is too large, the wettability of the electrolyte to the positive electrode film layer is poor, and the rate performance and cycle performance of the secondary battery may be affected, and the like, so that the situation can be effectively avoided. The solid-liquid contact angle between the positive electrode film layer and the non-aqueous organic solvent has a well-known meaning in the art, and can be tested using a method well-known in the art. For example, it can be measured with reference to GBT 30693-2014. One exemplary test method includes dropping a droplet of a non-aqueous organic solvent onto the surface of a positive electrode sheet at room temperature and measuring the contact angle for 60 seconds using a contact angle measuring device. The test device may be an LSA 200-type optical contact angle measuring device manufactured by LAUDA Scientific, Germany. The non-aqueous organic solvent may be any non-aqueous organic solvent used in non-aqueous electrolytes of secondary batteries that are well known in the art. Alternatively, the non-aqueous organic solvent may be ethylene carbonate (EC).

[0159] In some embodiments, the porosity of the positive electrode membrane layer is 15% to 50%, and optionally 15% to 30%. When the porosity is within an appropriate range, the secondary battery can have both high energy density and improved cycle performance, safety performance, and / or rate performance. In addition, if the porosity is too small, the wettability of the electrolyte to the positive electrode membrane layer is poor, which may affect the rate performance and cycle performance of the secondary battery, and if the porosity is too large, it may affect the energy density of the entire secondary battery. The porosity of the positive electrode membrane layer has a meaning well known in the art and can be measured by a method well known in the art. For example, it can be measured by referring to GB / T 24586-2009 after peeling off the positive electrode membrane layer with an adhesive tape. The porosity P=[(V2-V1) / V2]×100%. V1(cm 3 ) represents the true volume and can be measured by combining Archimedes' principle and Bohr's law using a displacement method with an inert gas (e.g., helium gas) having a small molecular diameter. V(cm 3 ) represents the apparent volume, V2 = S × H × A, S (cm 2 ) represents the area, H (cm) represents the thickness, and A represents the number of samples.

[0160] In some embodiments, the resistance of the positive electrode film layer is greater than 0 and less than or equal to 6Ω. This can ensure that the positive electrode sheet has good conductive ability and the secondary battery has better dynamic performance. The resistance of the positive electrode film layer has a well-known meaning in the art and can be tested using a well-known method in the art, for example, using an electrode sheet resistor. One exemplary measurement method is to place a positive electrode sheet coated on one side and cold-pressed (if the positive electrode sheet is coated on both sides, the positive electrode film layer is wiped off on one side first) in parallel between two conductive terminals of an electrode sheet resistor, and fix it by applying a certain pressure to obtain the resistance of the positive electrode film layer. Optionally, the diameter of the conductive terminals can be 14mm, the applied pressure can be 15MPa to 27Mpa, and the time range of the sample point can be 10 seconds to 20 seconds. The test equipment can adopt an IESTBER1000 type electrode sheet resistor, which is from Yuan Neng Technology Co., Ltd.

[0161] In some embodiments, the adhesive strength between the positive electrode film layer and the positive electrode current collector is 0.5 MPa or more. In this range, the occurrence of powder falling phenomenon of the positive electrode sheet can be prevented, which is advantageous for exerting secondary battery performance. The adhesive strength between the positive electrode film layer and the positive electrode current collector has a meaning well known in the art, and can be tested using a method well known in the art. In one exemplary test method, the positive electrode sheet is cut into a test sample having a length of 100 mm and a width of 10 mm, a stainless steel plate having a width of 25 mm is taken, and a double-sided tape (e.g., a width of 11 mm) is attached to the test sample. The test sample is attached to the double-sided tape of the stainless steel plate, and the surface is reciprocated three times with a 2000 g press roll (e.g., roll press speed 300 mm / min), the test sample is bent 180°, and the positive electrode film layer and the positive electrode current collector of the test sample are manually peeled off by 25 mm. The test sample is fixed to a test machine (e.g., INSTRON336), the peeling surface is aligned with the force line of the test machine, and the test machine is continuously peeled off at 30 mm / min to obtain a peel force curve, and the average value of the flat segments is the peel force F. 0 The adhesive strength between the positive electrode film layer and the positive electrode current collector is F 0 / Width of the test sample.

[0162] In some embodiments, the areal density of the positive electrode film layer is 0.006 g / cm 2 ~0.065g / cm 2 This is advantageous in improving the volumetric energy density of the secondary battery. The areal density of the positive electrode film layer has a meaning well known in the art, and can be tested using a method well known in the art. In one exemplary test method, a positive electrode sheet that is coated on one side and cold pressed (if the positive electrode sheet is coated on both sides, the positive electrode film layer on one side is first wiped off) is placed on a surface having an area of ​​S 1 The wafer is punched out into small wafers, and the weight of each wafer is measured. 1 The positive electrode film layer of the weighed positive electrode sheet is then wiped off, and the weight of the positive electrode current collector is weighed. 0 The areal density of the positive electrode layer is recorded as (M 1 -M 0 ) / S 1 It is.

[0163] In some embodiments, the positive electrode membrane layer has an absorption rate of the electrolyte of 0.0125 μg / s to 100 μg / s, and optionally 0.5 μg / s to 40 μg / s, which ensures that the electrolyte has good wettability with the electrode assembly, allows the electrolyte to quickly enter the inside of the electrode assembly, and promptly forms a new SEI film on the surface of the positive electrode sheet, thereby improving the electrochemical performance of the secondary battery.

[0164] The positive electrode membrane layer is usually formed by applying a positive electrode slurry to a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is usually formed by dispersing a positive electrode active material, an optional conductive agent, an optional adhesive, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).

[0165] In addition, the parameters of each positive electrode film layer provided in this application (e.g., contact angle, porosity, resistance, adhesive strength, surface density, electrolyte absorption rate, etc.) all refer to the parameters of the positive electrode film layer on one side of the positive electrode current collector. When positive electrode film layers are provided on both sides of the positive electrode current collector, it is considered that the parameters of either one of the positive electrode film layers satisfy the present application and fall within the protection scope of this application.

[0166] The testing of each parameter of the positive electrode film layer may be performed by sampling during the manufacturing process of the positive electrode sheet or the battery, or by sampling from the manufactured battery.

[0167] When the test sample is sampled from a manufactured battery, for example, the battery is discharged (for safety reasons, the battery is generally fully discharged), the battery is disassembled, and the positive electrode sheet is removed. The positive electrode sheet is then immersed in dimethyl carbonate (DMC) for a certain time (e.g., 2 hours to 10 hours), and then the positive electrode sheet is removed and dried at a certain temperature and time (e.g., 60°C, 4 hours). After drying, the positive electrode sheet is removed, and the dried positive electrode sheet is sampled to test each parameter related to the positive electrode film layer of the present application. secondary battery

[0168] A fourth aspect of the present application provides a secondary battery including the positive electrode sheet of the third aspect of the present application.

[0169] A secondary battery, also called a rechargeable battery or storage battery, is a battery that can continue to be used by activating the active material by charging after discharging the battery. Typically, a secondary battery includes an electrode assembly and an electrolyte, and the electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is disposed between the positive electrode sheet and the negative electrode sheet, and mainly serves to prevent short circuits between the positive and negative electrodes, while allowing active ions to pass through. The electrolyte serves to conduct active ions between the positive electrode sheet and the negative electrode sheet. [Positive electrode sheet]

[0170] The positive electrode sheet used in the secondary battery of the present application is the positive electrode sheet described in any one of the examples of the third aspect of the present application. [Negative electrode sheet]

[0171] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer that is provided on at least one surface of the negative electrode current collector and contains a negative electrode active material. For example, the negative electrode current collector has two surfaces that face each other in a thickness direction, and the negative electrode film layer is provided on one or both of the two facing surfaces of the negative electrode current collector.

[0172] The negative electrode active material may be any negative electrode active material for secondary batteries known in the art. For example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based material, tin-based material, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon carbon composite, silicon nitrogen composite, and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide, and tin alloy material. The present application is not limited to these materials, and other materials known in the art that are used as negative electrode active materials for secondary batteries may be used. These negative electrode active materials may be used alone or in combination of two or more types.

[0173] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent, optionally. In the present application, the type of the negative electrode conductive agent is not particularly limited. For example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0174] In some embodiments, the negative electrode membrane layer may further include a negative electrode adhesive, optionally. In the present application, the type of the negative electrode adhesive is not particularly limited. For example, the negative electrode adhesive may include at least one of styrene butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0175] In some embodiments, the negative electrode membrane layer may optionally further include other auxiliary agents. For example, the other auxiliary agents may include thickeners such as sodium carboxymethylcellulose (CMC), PTC thermistor materials, etc.

[0176] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. An example of the metal foil may be copper foil. The composite current collector may include a polymeric material base layer and a metal material layer formed on at least one surface of the polymeric material base layer. For example, the metal material may be at least one selected from copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. For example, the polymeric material base layer may be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), and the like.

[0177] The negative electrode film layer is typically formed by applying a negative electrode slurry to a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is typically formed by dispersing a negative electrode active material, an optional conductive agent, an optional adhesive, and other optional auxiliary agents in a solvent and uniformly stirring the mixture. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.

[0178] The negative electrode sheet does not exclude additional functional layers other than the negative electrode film layer. For example, in some embodiments, the negative electrode sheet according to the present application further includes a conductive primer layer (e.g., made of a conductive agent and an adhesive) sandwiched between the negative electrode collector and the negative electrode film layer and provided on the surface of the negative electrode collector. In some other embodiments, the negative electrode sheet described in the present application further includes a protective layer covering the surface of the negative electrode film layer. [Electrolyte]

[0179] In the present application, the type of the electrolyte is not particularly limited and can be selected according to requirements. For example, the electrolyte may be at least one selected from a solid electrolyte and a liquid electrolyte (electrolytic solution).

[0180] In some embodiments, the electrolyte employs an electrolytic solution, the electrolytic solution including an electrolyte salt and a solvent.

[0181] The type of the electrolyte salt is not particularly limited and can be selected according to actual requirements. In some embodiments, for example, the electrolyte salt is lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ), lithium hexafluoroarsenate (LiAsF 6 ), lithium bisfluorosulfonylimide (LiFSI), lithium bistrifluoromethanesulfonylimide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium disoxalate borate (LiBOB), lithium difluorophosphate (LiPO 2 F 2 ), lithium difluorooxalophosphate (LiDFOP), and lithium tetrafluorooxalophosphate (LiTFOP).

[0182] The type of solvent is not particularly limited and can be selected according to actual requirements.In some embodiments, as an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).

[0183] In some embodiments, the electrolyte may further include an optional additive. For example, the additive may include a negative electrode film-forming additive, a positive electrode film-forming additive, or an additive that can improve some performance of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature performance of the battery, or an additive that improves the low temperature power performance of the battery. [Separator]

[0184] In secondary batteries using an electrolytic solution or a secondary battery using a solid electrolyte, a separator is also included. The separator is provided between the positive electrode sheet and the negative electrode sheet, and mainly serves to prevent short-circuiting of the positive and negative electrodes, while allowing active ions to pass through. In the present application, the type of the separator is not particularly limited, and any well-known porous structure separator having good chemical stability and mechanical stability can be selected.

[0185] In some embodiments, the material of the separator may include at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a monolayer film or a multilayer composite film. When the separator is a multilayer composite film, the materials of each layer may be the same or different.

[0186] In some embodiments, the positive electrode sheet, the separator and the negative electrode sheet can be produced into an electrode assembly by a winding process or a stacking process.

[0187] In some embodiments, the secondary battery may include an exterior case that is used to seal the electrode assembly and electrolyte described above.

[0188] In some embodiments, the exterior of the secondary battery may be a hard package such as a hard plastic case, an aluminum case, or a steel case. The exterior of the secondary battery may be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0189] In the present application, the shape of the secondary battery is not particularly limited, and may be cylindrical, rectangular, or any other shape. Fig. 1 shows a secondary battery 5 having a rectangular structure as an example.

[0190] In some embodiments, as shown in FIG. 2, the exterior may include a case 51 and a cover plate 53. The case 51 includes a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are surrounded to form a chamber. The case 51 has an opening communicating with the chamber, and the cover plate 53 covers the opening to seal the chamber. The positive electrode sheet, the negative electrode sheet and the separator can form an electrode assembly 52 by a winding process and / or a stacking process. The electrode assembly 52 is packaged in the chamber. The electrolyte is permeated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and may be adjusted according to requirements.

[0191] The method for manufacturing the secondary battery of the present application is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte solution can be assembled to form a secondary battery. For example, a positive electrode sheet, a separator, and a negative electrode sheet can be formed into an electrode assembly by a winding process or a lamination process, and the electrode assembly can be placed in an outer casing, dried, and then an electrolyte solution can be injected, and a secondary battery can be obtained through processes such as vacuum sealing, standing, chemical formation, and shaping.

[0192] In some embodiments of the present application, the secondary battery of the present application may be assembled into a battery module, and the number of secondary batteries included in the battery module may be multiple, and the specific number may be adjusted according to the application and capacity of the battery module.

[0193] Fig. 3 is a schematic diagram of an example battery module 4. As shown in Fig. 3, in the battery module 4, the multiple secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by a fastener.

[0194] Optionally, the battery module 4 further includes a case having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.

[0195] In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules included in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0196] 4 and 5 are schematic diagrams of an example battery pack 1. As shown in Fig. 4 and 5, the battery pack 1 may include a battery case and a plurality of battery modules 4 provided in the battery case. The battery case includes an upper case 2 and a lower case 3, and the upper case 2 covers the lower case 3 to form an enclosed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery case in any manner. power consumption equipment

[0197] A fifth aspect of the present application provides a power consuming device including at least one of the secondary batteries, battery modules, or battery packs of the present application. The secondary batteries, battery modules, or battery packs may be used as a power source for the power consuming device, or may be used as an energy storage means for the power consuming device. The power consuming device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), a train, a ship, and a satellite, an energy storage system, etc.

[0198] The power consumption device can select a secondary battery, a battery module or a battery pack according to the demand.

[0199] 6 is a schematic diagram of an example power consuming device, such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. A battery pack or a battery module may be employed to meet the high power and high energy density requirements of the power consuming device.

[0200] Another example of the power consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. This power consuming device is usually required to be thin and may employ a secondary battery as a power source. Working Example

[0201] The following examples are provided to more specifically describe the contents of the present application, but these examples are merely illustrative, and it is obvious to those skilled in the art that various modifications and changes may be made within the scope of the disclosure of the present application. All quantities, percentages, and ratios described in the following examples are based on mass unless otherwise specified. In addition, all reagents used in the examples are commercially available or may be synthesized according to conventional methods, and can be used as is without further treatment. In addition, all devices used in the examples are commercially available.

[0202] [Table 0] Example 1-1 Manufacture of positive electrode active material (1) Preparation of co-doped lithium manganese phosphate cores

[0203] Preparation of Fe, Co and V co-doped manganese oxalate: Manganese carbonate (MnCO 3 (Calculation below) 689.5g, ferrous carbonate (FeCO 3 (Calculation is as follows) 455.2g, cobalt sulfate (CoSO 4 (Calculation is as follows) 4.6g, vanadium dichloride (VCl 2 Mix 4.9g of oxalic acid dihydrate (C 100.6g) thoroughly in a mixer for 6 hours. Transfer the mixture to a reaction vessel and add 5 liters of deionized water and 1260.6g of oxalic acid dihydrate (C 100.6g). 2 H 2 O 4 .2H 2The reaction vessel is heated to 80°C and stirred at a rotation speed of 600 rpm for 6 hours until the reaction is completed (no bubbles are generated), to obtain a manganese oxalate suspension co-doped with Fe, Co, V and S. The suspension is then filtered, and the cake is dried at 120°C, and then polished to obtain manganese oxalate dihydrate particles co-doped with Fe, Co and V, with a median diameter Dv50 of 100 nm.

[0204] Preparation of lithium manganese phosphate co-doped with Fe, Co, V, and S: Manganese oxalate dihydrate particles (1793.4 g) obtained in the previous step, 369.0 g of lithium carbonate (Li 2 CO 3 (Calculation is based on the following formula, and the same applies below), 60% dilute sulfuric acid (60%H 2 SO 4 (Calculations are as follows) 1.6 g, ammonium dihydrogen phosphate 1148.9 g (NH 4 H 2 PO 4 (Calculation: 1148.9g, same below) is added to 20L of deionized water, and the mixture is stirred for 10 hours to mix uniformly to obtain a slurry. The above slurry is transferred to a spray drying device and spray-dried to granulate, the drying temperature is set to 250°C, and dried for 4 hours to obtain a powder material. The above powder material is sintered at 700°C for 4 hours in a protective atmosphere of nitrogen gas (90% by volume) + hydrogen gas (10% by volume) to obtain 1572.1g of cores, which are lithium manganese phosphate co-doped with Fe, Co, V and S. (2) Manufacture of lithium iron pyrophosphate and lithium iron phosphate

[0205] Preparation of lithium iron pyrophosphate powder: 4.77 g of lithium carbonate, 7.47 g of ferrous carbonate, 14.84 g of ammonium dihydrogen phosphate, and 1.3 g of oxalic acid dihydrate are dissolved in 50 mL of deionized water. The pH of the mixture is 5, and the mixture is stirred for 2 hours to fully react. The solution after the reaction is then heated to 80°C and kept at that temperature for 4 hours to obtain Li 2 FeP 2 O 7The suspension is filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder is sintered at 650°C for 8 hours in a nitrogen gas atmosphere, naturally cooled to room temperature, and then polished to obtain Li 2 FeP 2 O 7 A powder is obtained.

[0206] Preparation of lithium iron phosphate suspension: 11.1 g lithium carbonate, 34.8 g ferrous carbonate, 34.5 g ammonium dihydrogen phosphate, 1.3 g oxalic acid dihydrate, sucrose (C 12 H 22 O 11 (Calculation is as follows) 74.6 g of LiFePO was dissolved in 150 mL of deionized water to obtain a mixture, which was then stirred for 6 hours to allow the mixture to react sufficiently. After that, the solution after the reaction was heated to 120°C and kept at that temperature for 6 hours to obtain LiFePO 4 A suspension containing (3) Covering

[0207] The Fe, Co, V and S co-doped lithium manganese phosphate (core) of 1572.1 g and the lithium iron pyrophosphate (Li 2 FeP 2 O 7 ) powder produced in the previous process, 4 ) suspension, and after stirring and mixing uniformly, it is transferred to a vacuum oven and dried at 150°C for 6 hours. The product is then dispersed using a sand mill. After dispersion, the resulting product is sintered in a nitrogen gas atmosphere at 700°C for 6 hours to obtain the desired product, lithium manganese phosphate coated with a double layer, i.e., the positive electrode active material. Manufacture of positive electrode sheets

[0208] The positive electrode active material is acetylene black as a conductive agent, and the adhesive is polyvinylidene fluoride (PVDF) and aminoethylaminopropylpolydimethylsiloxane (with the polar functional group -CH 2 NH 2 and -CH 2NH-, mass percentage α is about 12%, number average molecular weight is 3700) is stirred in a mixer in a weight ratio of 93.4:1.5:4.5:0.6 until the materials are uniformly mixed to obtain a positive electrode material composition. Next, the positive electrode material composition is added to N-methylpyrrolidone (NMP) and stirred to uniformly mix to obtain a positive electrode slurry. The positive electrode slurry is then applied to a substrate with a coating surface density of 0.018 g / cm 2 The mixture is evenly applied to aluminum foil, which is then dried, cold pressed, and slit to obtain the positive electrode sheet. Manufacture of negative electrode sheets

[0209] The negative electrode active materials, artificial graphite, hard carbon, acetylene black as a conductive agent, styrene butadiene rubber (SBR) as an adhesive, and sodium carboxymethyl cellulose (CMC) as a thickener are dissolved in deionized water as a solvent in a weight ratio of 90:5:2:2:1, and then stirred to mix uniformly to produce the negative electrode slurry. The negative electrode slurry is applied to a surface density of 0.0075 g / cm. 2 The paste is then evenly applied to the copper foil of the negative electrode current collector, which is then dried, cold pressed, and slit to obtain the negative electrode sheet. Electrolyte production

[0210] In a glove box with an argon gas atmosphere (H 2 O<0.1ppm, O 2 <0.1 ppm) was mixed uniformly with ethylene carbonate (EC) / ethyl methyl carbonate (EMC) as an organic solvent in a volume ratio of 3 / 7, and 12.5 wt % (calculated based on the weight of the organic solvent) of LiPF was added to the organic solvent. 6 The mixture is added and dissolved, and the mixture is stirred uniformly to obtain an electrolyte solution. Separator manufacturing

[0211] A commercially available microporous film of PP-PE copolymer with a thickness of 20 μm and an average pore size of 80 nm (Zhuoga Electronics Technology Co., Ltd., Model 20) was used. Full cell manufacturing

[0212] The positive electrode sheet, separator, and negative electrode sheet obtained above are stacked in this order, the separator is placed between the positive electrode and the negative electrode to perform the function of separation, and then wound to obtain an electrode assembly. The electrode assembly is placed in an outer casing, the above electrolyte is injected, and the assembly is sealed to obtain a full cell. Coin Cell Manufacturing

[0213] The positive electrode active material is acetylene black as a conductive agent, and the adhesive is polyvinylidene fluoride (PVDF) and aminoethylaminopropylpolydimethylsiloxane (with the polar functional group -CH 2 NH 2 and -CH 2 NH-, mass percentage α of about 12%, number average molecular weight of 3700) are stirred in a mixer at a weight ratio of 89.4:5:5:0.6 until the materials are uniformly mixed to obtain a positive electrode material composition. The positive electrode material composition is then added to NMP and stirred in a drying chamber to obtain a slurry. The slurry is applied to an aluminum foil, dried, and cold pressed to produce a positive electrode sheet. The surface density of the coating is 0.015 g / cm 2 , compression density is 2.0g / cm 3 It is.

[0214] A lithium sheet was used as the negative electrode, and 1 mol / L of LiPF was added to ethylene carbonate (EC) + diethyl carbonate (DEC) + dimethyl carbonate (DMC) in a volume ratio of 1:1:1. 6 The solution is adopted as the electrolyte, and a coin cell is assembled in a coin cell box together with the positive electrode sheet prepared above. Examples 1-2 to 1-33

[0215] Except for the preparation of the positive electrode active material, the other steps are the same as the process of Example 1-1. Examples 1-2 to 1-6

[0216] Manufacture of positive electrode active materialThe manufacturing conditions of the lithium manganese phosphate core in Examples 1-2 to 1-6 are the same as those in Example 1-1, except that in the manufacturing process of the co-doped lithium manganese phosphate core, vanadium dichloride and cobalt sulfate were not used, and 463.4 g of ferrous carbonate, 1.6 g of dilute sulfuric acid with a concentration of 60%, 1148.9 g of ammonium dihydrogen phosphate, and 369.0 g of lithium carbonate were used. In addition, in the manufacturing process of lithium iron pyrophosphate and lithium iron phosphate and the process of coating the first coating layer and the second coating layer, the raw materials used were adjusted according to the ratio of the coating amount shown in Table 1 to the coating amount corresponding to Example 1-1, and the Li in Examples 1-2 to 1-6 were obtained. 2 FeP 2 O 7 / LiFePO 4 The other conditions were the same as in Example 1-1, except that the amounts of sucrose used in Examples 1-2 to 1-6 were 37.3 g, and the amounts of sucrose used in Examples 1-2 to 1-6 were 12.6 g / 37.7 g, 15.7 g / 47.1 g, 18.8 g / 56.5 g, 22.0 g / 66.0 g, and 25.1 g / 75.4 g, respectively. Examples 1-7 to 1-10

[0217] Manufacture of positive electrode active material The conditions of Examples 1-7 to 1-10 were the same as those of Example 1-3, except that the amounts of sucrose used were 74.6 g, 149.1 g, 186.4 g, and 223.7 g, respectively, so that the corresponding coating amounts of the carbon layer as the second coating layer were 31.4 g, 62.9 g, 78.6 g, and 94.3 g, respectively. Examples 1-11 to 1-14

[0218] Manufacture of positive electrode active material In the manufacturing process of lithium iron pyrophosphate and lithium iron phosphate, the amount of each raw material used is adjusted according to the coating amount shown in Table 1. 2 FeP 2 O 7 / LiFePO 4The conditions of Examples 1-11 to 1-14 were the same as those of Example 1-7, except that the amounts of the components used were 23.6 g / 39.3 g, 31.4 g / 31.4 g, 39.3 g / 23.6 g, and 47.2 g / 15.7 g, respectively. Examples 1-15

[0219] Manufacture of positive electrode active material The conditions of Example 1-15 were the same as those of Example 1-14, except that 492.80 g of zinc carbonate was used instead of ferrous carbonate in the preparation of the co-doped lithium manganese phosphate core. Examples 1-16 to 1-18

[0220] Manufacture of positive electrode active material The conditions of Examples 1-16 to 1-18 were the same as those of Example 1-7, except that in Example 1-16, 466.4 g of nickel carbonate, 5.0 g of zinc carbonate, and 7.2 g of titanium sulfate were used instead of ferrous carbonate in the process for producing the co-doped lithium manganese phosphate core, in Example 1-17, 455.2 g of ferrous carbonate and 8.5 g of vanadium dichloride were used in the process for producing the co-doped lithium manganese phosphate core, and in Example 1-18, 455.2 g of ferrous carbonate, 4.9 g of vanadium dichloride, and 2.5 g of magnesium carbonate were used in the process for producing the co-doped lithium manganese phosphate core. Examples 1-19 to 1-20

[0221] Manufacture of positive electrode active material The conditions of Examples 1-19 to 1-20 are the same as those of Example 1-18, except that in Example 1-19, 369.4 g of lithium carbonate was used and 1.05 g of 60% dilute nitric acid was used instead of dilute sulfuric acid in the process of producing the co-doped lithium manganese phosphate core, and in Example 1-20, 369.7 g of lithium carbonate was used and 0.78 g of silicic acid was used instead of dilute sulfuric acid in the process of producing the co-doped lithium manganese phosphate core. Examples 1-21 to 1-22

[0222] Manufacture of positive electrode active materialThe conditions of Examples 1-21 and 1-22 were the same as those of Example 1-20, except that in Example 1-21, 632.0 g of manganese carbonate, 463.30 g of ferrous carbonate, 30.5 g of vanadium dichloride, 21.0 g of magnesium carbonate, and 0.78 g of silicic acid were used in the preparation of the co-doped lithium manganese phosphate core, and in Example 1-22, 746.9 g of manganese carbonate, 289.6 g of ferrous carbonate, 60.9 g of vanadium dichloride, 42.1 g of magnesium carbonate, and 0.78 g of silicic acid were used in the preparation of the co-doped lithium manganese phosphate core. Examples 1-23 to 1-24

[0223] Manufacture of positive electrode active material The conditions of Examples 1-23 to 1-24 are the same as those of Example 1-22, except that in Example 1-23, 804.6 g of manganese carbonate, 231.7 g of ferrous carbonate, 1156.2 g of ammonium dihydrogen phosphate, 1.2 g of boric acid (mass fraction 99.5%) and 370.8 g of lithium carbonate were used in the production process of the co-doped lithium manganese phosphate core, and in Example 1-24, 862.1 g of manganese carbonate, 173.8 g of ferrous carbonate, 1155.1 g of ammonium dihydrogen phosphate, 1.86 g of boric acid (mass fraction 99.5%) and 371.6 g of lithium carbonate were used in the production process of the co-doped lithium manganese phosphate core. Examples 1-25

[0224] Manufacture of positive electrode active material The conditions of Example 1-25 are the same as those of Example 1-20, except that 370.1 g of lithium carbonate, 1.56 g of silicic acid, and 1147.7 g of ammonium dihydrogen phosphate were used in the preparation of the co-doped lithium manganese phosphate core. Examples 1-26

[0225] Manufacture of positive electrode active materialThe conditions of Example 1-26 were the same as those of Example 1-20, except that 368.3 g of lithium carbonate, 4.9 g of 60% by mass dilute sulfuric acid, 919.6 g of manganese carbonate, 224.8 g of ferrous carbonate, 3.7 g of vanadium dichloride, 2.5 g of magnesium carbonate, and 1146.8 g of ammonium dihydrogen phosphate were used in the preparation of the co-doped lithium manganese phosphate core. Examples 1-27

[0226] Manufacture of positive electrode active material The conditions of Example 1-27 were the same as those of Example 1-20, except that 367.9 g of lithium carbonate, 6.5 g of 60% dilute sulfuric acid, and 1145.4 g of ammonium dihydrogen phosphate were used in the preparation of the co-doped lithium manganese phosphate core. Examples 1-28 to 1-33

[0227] Manufacture of positive electrode active material In the manufacturing process of the co-doped lithium manganese phosphate core, the following conditions were used: manganese carbonate 1034.5g, ferrous carbonate 108.9g, vanadium dichloride 3.7g, and magnesium carbonate 2.5g; the amounts of lithium carbonate used were 367.6g, 367.2g, 366.8g, 366.4g, 366.0g, and 332.4g, respectively; the amounts of ammonium dihydrogen phosphate used were 1144.5g, 1143.4g, 1142.2g, 1141.1g, 1139.9g, and 1138.8g, respectively; and the amounts of dilute sulfuric acid with a concentration of 60% were 8.2g, 9.8g, 11.4g, 13.1g, 14.7g, and 16.3g, respectively. Examples 2-1 to 2-3

[0228] In addition to the preparation of the positive electrode active material, other conditions are the same as the process of Example 1-1. Example 2-1

[0229] Manufacture of positive electrode active material : Lithium iron pyrophosphate (Li 2 FeP 2 O7 In the manufacturing process of Li, the sintering temperature in the powder sintering process is set to 550°C, and the sintering time is set to 1 hour. 2 FeP 2 O 7 The crystallinity of lithium iron phosphate (LiFePO 4 In the manufacturing process of LiFePO, the sintering temperature in the coating sintering process was set to 650°C, and the sintering time was set to 2 hours. 4 The other conditions were the same as in Example 1-1, except that the crystallinity of was controlled to be 30%. Example 2-2

[0230] Manufacture of positive electrode active material : Lithium iron pyrophosphate (Li 2 FeP 2 O 7 In the manufacturing process of Li, the sintering temperature in the powder sintering process is set to 550°C, the sintering time is set to 2 hours, and 2 FeP 2 O 7 The crystallinity of lithium iron phosphate (LiFePO 4 In the manufacturing process of LiFePO, the sintering temperature in the coating sintering process was set to 650°C, and the sintering time was set to 3 hours. 4 The other conditions were the same as in Example 1-1, except that the crystallinity of was controlled to be 50%. Example 2-3

[0231] Manufacture of positive electrode active material : Lithium iron pyrophosphate (Li 2 FeP 2 O 7 In the manufacturing process of Li, the sintering temperature in the powder sintering process is set to 600°C, the sintering time is set to 3 hours, and 2 FeP 2 O 7 The crystallinity of lithium iron phosphate (LiFePO 4 In the manufacturing process of LiFePO, the sintering temperature in the coating sintering process was set to 650°C, the sintering time was set to 4 hours, and 4 The other conditions were the same as in Example 1-1, except that the crystallinity of was controlled to be 70%. Examples 3-1 to 3-5

[0232] In the production of the full cell and the coin cell, the weight percentage of aminoethylaminopropylpolydimethylsiloxane in the positive electrode material composition was adjusted, but the other conditions were all the same as those in the process of Example 1-1. Example 3-1

[0233] Full cell manufacturing : Positive electrode active material, acetylene black as a conductive agent, polyvinylidene fluoride (PVDF) as an adhesive, and aminoethylaminopropylpolydimethylsiloxane (polar functional group is -CH 2 NH 2 and -CH 2 NH-, mass percentage α is about 12%, number average molecular weight is 3700) are stirred in a mixer in a weight ratio of 93.99:1.5:4.5:0.01 until the materials are uniformly mixed to obtain a positive electrode material composition.

[0234] Coin Cell Manufacturing : Positive electrode active material, acetylene black as a conductive agent, polyvinylidene fluoride (PVDF) as an adhesive, and aminoethylaminopropylpolydimethylsiloxane (polar functional group is -CH 2 NH 2 and -CH 2 NH-, mass percentage α is about 12%, number average molecular weight is 3700) are stirred in a mixer in a weight ratio of 89.99:5:5:0.01 until the materials are uniformly mixed to obtain a positive electrode material composition. Example 3-2

[0235] Full cell manufacturing : Positive electrode active material, acetylene black as a conductive agent, polyvinylidene fluoride (PVDF) as an adhesive, and aminoethylaminopropylpolydimethylsiloxane (polar functional group is -CH 2 NH 2 and -CH 2 NH-, mass percentage α is about 12%, number average molecular weight is 3700) are stirred in a mixer in a weight ratio of 93.9:1.5:4.5:0.1 until the materials are uniformly mixed to obtain a positive electrode material composition.

[0236] Coin Cell Manufacturing : Positive electrode active material, acetylene black as a conductive agent, polyvinylidene fluoride (PVDF) as an adhesive, and aminoethylaminopropylpolydimethylsiloxane (polar functional group is -CH 2 NH 2 and -CH 2 NH-, mass percentage α is about 12%, number average molecular weight is 3700) are stirred in a mixer in a weight ratio of 89.9:5:5:0.1 until the materials are uniformly mixed to obtain a positive electrode material composition. Example 3-3

[0237] Full cell manufacturing : Positive electrode active material, acetylene black as a conductive agent, polyvinylidene fluoride (PVDF) as an adhesive, and aminoethylaminopropylpolydimethylsiloxane (polar functional group is -CH 2 NH 2 and -CH 2 NH-, mass percentage α is about 12%, number average molecular weight is 3700) are stirred in a mixer in a weight ratio of 93:1.5:4.5:1 until the materials are uniformly mixed to obtain a positive electrode material composition.

[0238] Coin Cell Manufacturing : Positive electrode active material, acetylene black as a conductive agent, polyvinylidene fluoride (PVDF) as an adhesive, and aminoethylaminopropylpolydimethylsiloxane (polar functional group is -CH 2 NH 2 and -CH 2 NH-, mass percentage α is about 12%, number average molecular weight is 3700) are stirred in a mixer in a weight ratio of 89:5:5:1 until the materials are uniformly mixed to obtain a positive electrode material composition. Examples 3-4

[0239] Full cell manufacturing : Positive electrode active material, acetylene black as a conductive agent, polyvinylidene fluoride (PVDF) as an adhesive, and aminoethylaminopropylpolydimethylsiloxane (polar functional group is -CH 2 NH 2 and -CH 2NH-, mass percentage α is about 12%, number average molecular weight is 3700) are stirred in a mixer in a weight ratio of 92:1.5:4.5:2 until the materials are uniformly mixed to obtain a positive electrode material composition.

[0240] Coin Cell Manufacturing : Positive electrode active material, acetylene black as a conductive agent, polyvinylidene fluoride (PVDF) as an adhesive, and aminoethylaminopropylpolydimethylsiloxane (polar functional group is -CH 2 NH 2 and -CH 2 NH-, mass percentage α is about 12%, number average molecular weight is 3700) are stirred in a mixer in a weight ratio of 88:5:5:2 until the materials are uniformly mixed to obtain a positive electrode material composition. Examples 3-5

[0241] Full cell manufacturing : Positive electrode active material, acetylene black as a conductive agent, polyvinylidene fluoride (PVDF) as an adhesive, and aminoethylaminopropylpolydimethylsiloxane (polar functional group is -CH 2 NH 2 and -CH 2 NH-, mass percentage α is about 12%, number average molecular weight is 3700) are stirred in a mixer in a weight ratio of 89:1.5:4.5:5 until the materials are uniformly mixed to obtain a positive electrode material composition.

[0242] Coin Cell Manufacturing : Positive electrode active material, acetylene black as a conductive agent, polyvinylidene fluoride (PVDF) as an adhesive, and aminoethylaminopropylpolydimethylsiloxane (polar functional group is -CH 2 NH 2 and -CH 2 NH-, mass percentage α is about 12%, number average molecular weight is 3700) are stirred in a mixer in a weight ratio of 85:5:5:5 until the materials are uniformly mixed to obtain a positive electrode material composition. Examples 3-6 to 3-23

[0243] In the production of the full cell and the coin cell, the conditions were the same as those in the process of Example 1-1, except that the aminoethylaminopropylpolydimethylsiloxane in the positive electrode material composition was replaced with the following organopolysiloxane compounds, respectively.

[0244] Example 3-6: Polydimethylsiloxane (mass percentage α of polar functional groups is about 0%, number average molecular weight is 1200).

[0245] Example 3-7: Polymethylchloropropylsiloxane (polar functional group is -CH 2 Cl, mass percentage α is approximately 30.2%, number average molecular weight is approximately 2500).

[0246] Example 3-8: Polymethyltrifluoropropylsiloxane (polar functional group is -CF 3 , mass percentage α is approximately 44.0%, and number average molecular weight is approximately 1400).

[0247] Example 3-9: Mercaptopropyl polysiloxane (polar functional group is -CH 2 SH, mass percentage α is approximately 15.0%, and number average molecular weight is 2000).

[0248] Example 3-10: Hydroxy-terminated polydimethylsiloxane (polar functional group: -OH, mass percentage α: 3.4%, number average molecular weight: 1000).

[0249] Example 3-11: Methoxy-terminated polydimethylsiloxane (polar functional group is a methoxy group, mass percentage α is approximately 3.1%, number average molecular weight is 2800).

[0250] Example 3-12: Polyether-terminated polydimethylsiloxane (polar functional group is a polyether segment, mass percentage α is approximately 10.0%, and number average molecular weight is 2110).

[0251] Example 3-13: Side chain phosphate ester grafted polydimethylsiloxane (polar functional group is a phosphate ester group, mass percentage α is about 1.4%, number average molecular weight is 15600).

[0252] Example 3-14: 1,3,5,7-octamethylcyclotetrasiloxane (mass percentage α of polar functional groups is about 0%, molecular weight is 280).

[0253] Example 3-15: Cyclopentapolydimethylsiloxane (mass percentage α of polar functional groups is about 0%, molecular weight is 370).

[0254] Example 3-16: Polyether-terminated polydimethylsiloxane (polar functional group is a polyether segment, mass percentage α is approximately 55.0%, number average molecular weight is 25132).

[0255] Example 3-17: Polydimethylsiloxane (mass percentage α of polar functional groups is about 0%, number average molecular weight is 400).

[0256] Example 3-18: Polydimethylsiloxane (mass percentage α of polar functional groups is approximately 0%, number average molecular weight is 10,000).

[0257] Example 3-19: Polydimethylsiloxane (mass percentage α of polar functional groups is approximately 0%, number average molecular weight is 50,000).

[0258] Example 3-20: Polydimethylsiloxane (mass percentage α of polar functional groups is about 0%, number average molecular weight is 80,000).

[0259] Example 3-21: Polydimethylsiloxane (mass percentage α of polar functional groups is about 0%, number average molecular weight is 100,000).

[0260] Example 3-22: Polydimethylsiloxane (mass percentage α of polar functional groups is approximately 0%, number average molecular weight is 300,000).

[0261] Example 3-23: Polydimethylsiloxane (mass percentage α of polar functional groups is approximately 0%, number average molecular weight is 400,000). Comparative Examples 1 to 7

[0262] The positive electrode active material was prepared by the following method, and the process was the same as that of Example 1-1 except that aminoethylaminopropylpolydimethylsiloxane was not added to the positive electrode material composition in the preparation of the full cell and the coin cell. Comparative Example 1

[0263] Preparation of manganese oxalate: 1149.3 g of manganese carbonate was placed in a reaction vessel, and 5 liters of deionized water and 1260.6 g of oxalic acid dihydrate (C 2 H 2 O 4 2H 2 The reaction vessel is heated to 80°C and stirred at a rotation speed of 600 rpm for 6 hours until the reaction is completed (no bubbles are generated), to obtain a manganese oxalate suspension. The suspension is then filtered, and the cake is dried at 120°C, and then polished to obtain manganese oxalate dihydrate particles with a median diameter Dv50 of 100 nm.

[0264] Preparation of carbon-coated lithium manganese phosphate: 1789.6 g of the manganese oxalate dihydrate particles obtained above, 369.4 g of lithium carbonate (Li 2 CO 3 (Calculation is based on the following formula, and the same applies below), 1150.1 g of ammonium dihydrogen phosphate (NH 4 H 2 PO 4 (Calculation is as follows), sucrose (C 12 H 22 O 11 Add 31g of 10 ... Comparative Example 2

[0265] The other conditions of Comparative Example 2 were the same as those of Comparative Example 1, except that 689.5 g of manganese carbonate was used and 463.3 g of ferrous carbonate was added. Comparative Example 3

[0266] The other conditions of Comparative Example 3 were the same as those of Comparative Example 1, except that 1148.9 g of ammonium dihydrogen phosphate and 369.0 g of lithium carbonate were used and 1.6 g of dilute sulfuric acid with a concentration of 60% was added. Comparative Example 4

[0267] The other conditions of Comparative Example 4 were the same as those of Comparative Example 1, except that 689.5 g of manganese carbonate, 1148.9 g of ammonium dihydrogen phosphate, and 369.0 g of lithium carbonate were used, and 463.3 g of ferrous carbonate and 1.6 g of dilute sulfuric acid with a concentration of 60% were added. Comparative Example 5

[0268] Preparation of lithium iron pyrophosphate powder: 9.52 g of lithium carbonate, 29.9 g of ferrous carbonate, 29.6 g of ammonium dihydrogen phosphate, and 32.5 g of oxalic acid dihydrate are dissolved in 50 mL of deionized water. The pH of the mixture is 5, and the mixture is stirred for 2 hours to fully react. After that, the solution after the reaction is heated to 80°C and kept at that temperature for 4 hours to obtain Li 2 FeP 2 O 7 The suspension is filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder is sintered at 500°C for 4 hours in a nitrogen gas atmosphere, naturally cooled to room temperature, and then polished to obtain a Li 2 FeP 2 O 7 When the crystallinity of Li was controlled to 5% and a carbon-coated material was produced, 2 FeP 2 O 7 The amount of used is 62.8 g. Except for the addition of the above-mentioned step, the other conditions of Comparative Example 5 are the same as those of Comparative Example 4. Comparative Example 6

[0269] Preparation of lithium iron phosphate suspension: 14.7 g of lithium carbonate, 46.1 g of ferrous carbonate, 45.8 g of ammonium dihydrogen phosphate, and 50.2 g of oxalic acid dihydrate were dissolved in 500 mL of deionized water, and the mixture was stirred for 6 hours to react sufficiently. The solution after the reaction was heated to 120° C. and kept at that temperature for 6 hours to obtain LiFePO 4 and a step of obtaining a suspension consisting of lithium iron phosphate (LiFePO 4 In the manufacturing process of LiFePO, the sintering temperature in the coating sintering process was set at 600°C and the sintering time was set at 4 hours. 4 Except that the crystallinity of LiFePO was controlled to be 8% and when producing the carbon coated material, 4 The other conditions of Comparative Example 6 are the same as those of Comparative Example 4, except that the amount of used is 62.8 g. Comparative Example 7

[0270] Preparation of lithium iron pyrophosphate powder: 2.38 g of lithium carbonate, 7.5 g of ferrous carbonate, 7.4 g of ammonium dihydrogen phosphate, and 8.1 g of oxalic acid dihydrate are dissolved in 50 mL of deionized water. The pH of the mixture is 5, and the mixture is stirred for 2 hours to fully react. After that, the solution after the reaction is heated to 80°C and kept at that temperature for 4 hours to obtain Li 2 FeP 2 O 7 The suspension is filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder is sintered at 500°C for 4 hours in a nitrogen gas atmosphere, naturally cooled to room temperature, and then polished to obtain a Li 2 FeP 2 O 7 The crystallinity is controlled to be 5%.

[0271] Preparation of lithium iron phosphate suspension: 11.1 g lithium carbonate, 34.7 g ferrous carbonate, 34.4 g ammonium dihydrogen phosphate, 37.7 g oxalic acid dihydrate, 37.3 g sucrose (C 12 H 22 O 11(Calculation is based on the following formula, hereinafter the same) is dissolved in 1500 mL of deionized water, and the mixture is stirred for 6 hours to allow the mixture to react sufficiently. After that, the solution after the reaction is heated to 120°C and kept at that temperature for 6 hours to obtain LiFePO 4 A suspension containing

[0272] Coating: 15.7 g of the obtained lithium iron pyrophosphate powder was added to the lithium iron phosphate (LiFePO 4 ) and sucrose suspension, and in the manufacturing process, the sintering temperature in the coating sintering process was set to 600°C and the sintering time was set to 4 hours. 4 The other conditions of Comparative Example 7 were the same as those of Comparative Example 4, except that the crystallinity of the powder was controlled to be 8%, and amorphous lithium iron pyrophosphate, amorphous lithium iron phosphate, and a positive electrode active material coated with carbon were obtained. Comparative Example 8

[0273] In the preparation of the full cell and the coin cell, the other conditions are the same as those in the process of Example 1-1, except that aminoethylaminopropylpolydimethylsiloxane is not added. Testing correlation parameters 1. Determination of the chemical formula of the core and the composition of the different coating layers:

[0274] A spherical aberration corrected scanning transmission electron microscope (ACSTEM) is used to characterize the internal microstructure and surface structure of the positive electrode active material with high spatial resolution, and combined with 3D reconstruction techniques to obtain the chemical formula of the positive electrode active material core and the compositions of the first and second coating layers. 2. Coin cell initial gram capacity testing:

[0275] The coin cell obtained above is charged to 4.3 V at 0.1 C, then charged at a constant voltage of 4.3 V until the current becomes 0.05 mA or less, and after leaving it to stand for 5 minutes, it is discharged to 2.0 V at 0.1 C. The discharge capacity at this time is the initial gram capacity and is denoted as D0. 3. Coin cell average discharge voltage (V) test:

[0276] The coin cell obtained above is left to stand for 5 minutes in a constant temperature environment of 25°C, discharged at 0.1C to 2.5V, left to stand for 5 minutes, charged at 0.1C to 4.3V, then charged at a constant voltage of 4.3V until the current becomes 0.05mA or less, left to stand for 5 minutes, and then discharged at 0.1C to 2.5V. The discharge capacity at this time is the initial gram capacity and is noted as D0, the discharge energy is the initial energy and is noted as E0, and the average discharge voltage V of the coin cell is E0 / D0. 4. Full cell expansion test at 60℃:

[0277] The full cell obtained above with a 100% state of charge (SOC) is stored at 60°C. The open circuit voltage (OCV) and alternating current internal resistance (IMP) of the battery are measured before, during and after storage to monitor the SOC, and the volume of the battery is measured. After every 48 hours of storage, the full cell is removed and left to stand for one hour, after which the open circuit voltage (OCV) and internal resistance (IMP) are tested, and after cooling to room temperature, the volume of the battery is measured using the drainage method. In the drainage method, the gravity F of the battery is first measured using a balance that automatically converts the unit of the dial data. 1 The value was measured alone, and then the battery was completely filled with deionized water (with a known density of 1 g / cm 3 The battery is placed on the ground, and the gravity of the battery at this time is F 2 Measure the buoyancy force F 浮 is F 1 -F 2 and Archimedes' principle F 浮 = ρ × g × V 排 Based on this, the volume of the battery is V = (F 1 -F 2 ) / (ρ×g).

[0278] From the test results of OCV and IMP, the batteries of all the embodiments maintained SOC of 99% or more until the end of storage in this test process.

[0279] After storage for 30 days, the volume of the battery is measured and the percentage increase in the volume of the battery after storage relative to the volume of the battery before storage is calculated. 5. Full cell cycle performance test at 45℃:

[0280] The full cell obtained above is charged to 4.3 V at 1 C in a constant temperature environment of 45 ° C, and then charged at a constant voltage of 4.3 V until the current is 0.05 mA or less. After leaving it to stand for 5 minutes, it is discharged to 2.5 V at 1 C, and the discharge capacity at this time is recorded as D0. The above-mentioned charge and discharge cycle is repeated until the discharge capacity drops to 80% of D0. The number of cycles of the battery at this time is recorded. 6. Transition metal elution test:

[0281] The full cell was cycled at 45°C until the capacity was attenuated to 80%. The full cell was discharged at a rate of 0.1C to a cut-off voltage of 2.0V. The battery was then disassembled to remove the negative electrode sheet, and a unit area (1540.25 mm2) was placed on the negative electrode sheet. 2 ) wafers are randomly selected and tested for inductively coupled plasma emission spectrum (ICP) using an Agilent ICP-OES730. From the ICP results, the amount of Fe (if Fe is doped on the Mn site of the positive electrode active material) and Mn are calculated, and the amount of Mn (and Fe doped on the Mn site) eluted after cycling is calculated. The test standard complies with EPA-6010D-2014. 7.Measuring method of lattice change rate:

[0282] In a constant temperature environment of 25℃, the sample of the positive electrode active material obtained above is placed in an XRD (model Bruker D8 Discover), and the sample is tested at 1° / min. The test data is collated and analyzed, and the lattice constants a0, b0, c0 and v0 at this time are calculated by referring to a standard PDF card (a0, b0 and c0 indicate the length size in each direction of the unit lattice, and v0 indicates the volume of the unit lattice, which can be obtained directly from the correction result of XRD).

[0283] Using the above-mentioned coin cell manufacturing method, a sample of the positive electrode active material is manufactured into a coin cell, and the coin cell is charged at a small rate of 0.05C until the current decreases to 0.01C. Next, the positive electrode sheet in the coin cell is taken out and immersed in dimethyl carbonate (DMC) for 8 hours. After that, it is dried, the powder is scraped off, and particles with a particle size of less than 500 nm are selected. The volume v1 of the unit lattice is calculated by sampling in the same manner as the above-mentioned test fresh sample, and (v0~v1) / v0×100% is shown in the table as the lattice change rate (volume change rate of the unit lattice) before and after the complete insertion and extraction of lithium. 8. Li / Mn anti-structural defect concentration test:

[0284] The XRD results measured by the "lattice change rate measurement method" are compared with the PDF (Powder Diffraction File) card of a standard crystal to obtain the Li / Mn antistructure defect concentration. Specifically, the XRD results measured by the "lattice change rate measurement method" are introduced into the software of a general structure analysis system (GSAS) to automatically obtain a refined result including the site information of different atoms, and the Li / Mn antistructure defect concentration is obtained from the refined result. 9. Surface oxygen valence test:

[0285] 5 g of the sample of the positive electrode active material produced above is manufactured into a coin cell according to the manufacturing method of the coin cell described above. In addition, the coin cell is charged at a small rate of 0.05 C until the current drops to 0.01 C. Next, the positive electrode sheet in the coin cell is taken out and placed in dimethyl carbonate (DMC) and soaked for 8 hours. After that, it is dried, the powder is scraped off, and particles with a particle size of less than 500 nm are selected. The obtained particles are measured by electron energy loss spectroscopy (EELS, model of the equipment used: Talos F200S), and the energy loss edge structure (ELNES) is obtained, which reflects the state density and energy level distribution of the element. From the state density and energy level distribution, the number of occupied electrons is calculated by integrating the state density of the valence band, and the valence of the surface oxygen after charging is estimated. 10. Measurement of compaction degree:

[0286] 5 g of the positive electrode active material powder produced above was placed in a compaction mold (USA CARVER mold, model 13 mm) and the mold was set in a compaction density meter. A pressing force of 3 T (tons) was applied, and the thickness of the powder under the pressing force (thickness after decompression, the area of ​​the container for the test was 1540.25 mm 2 ) is read out on the instrument and the compaction degree is calculated using ρ = m / v. 11. Measuring the crystallinity of pyrophosphate and phosphate salts by X-ray diffraction:

[0287] Take 5 g of the positive electrode active material powder obtained above, and measure the total scattering intensity by X-ray, which is the sum of the scattering intensity of the entire spatial material, and is somewhat related only to the intensity of the primary radiation, the chemical structure, and the total number of electrons participating in the diffraction (i.e., mass), and is independent of the order state of the sample. Crystalline scattering and non-crystalline scattering are separated from the diffraction pattern, and the crystallinity is the ratio of the crystalline partial scattering to the total scattering intensity. 12. Lattice spacing and included angle:

[0288] 1 g of each of the positive electrode active material powders obtained above is filled into a 50 mL test tube, 10 mL of alcohol with a mass fraction of 75% is poured into the test tube, and then the mixture is thoroughly stirred and dispersed for 30 minutes. Then, an appropriate amount of the above solution is taken with a clean disposable plastic pipette and dropped onto a 300 mesh copper mesh, at this time, some of the powder remains on the copper mesh, and the copper mesh and the sample are transferred to the sample chamber of a TEM (TalosF200sG2) for testing, and the original image of the TEM test is obtained.

[0289] The original image obtained by the above TEM test is opened in DigitalMicrograph software, and a Fourier transform (automatically completed by the software after clicking) is performed to obtain the diffraction pattern. The lattice spacing can be obtained by measuring the distance from the diffraction spot to the center position in the diffraction pattern, and the included angle can be obtained by calculating based on Bragg's equation. 13. Powder resistivity measurement:

[0290] An appropriate amount of sample powder of the positive electrode material composition for full cell manufacturing is placed in the special mold of the powder resistivity tester, and the test pressure can be set to obtain the powder resistivity at different pressures. In this application, the test pressure is 12Mpa. The test equipment is Suzhou Jingge ST2722-SZ type four-probe powder resistivity tester. 14.Specific surface area test:

[0291] 5 g of sample powder of the positive electrode material composition for full cell manufacturing is taken, and the specific surface area is tested using a Tri-Star 3020 specific surface area pore size analysis tester manufactured by Micromeritics, Inc., USA. The specific surface area is calculated by the BET (Brunauer Emmett Teller) method. 15.Contact angle test:

[0292] At room temperature, a droplet of ethylene carbonate (EC) is dropped onto the surface of the positive electrode film layer, and the solid-liquid contact angle is measured for 60 seconds using an optical contact angle measuring instrument LSA 200 manufactured by LAUDA Scientific, Germany.

[0293] Table 1 shows the compositions of the positive electrode active materials of Examples 1-1 to 1-33 and Comparative Examples 1 to 8.

[0294] Table 2 shows the types and contents of organopolysiloxane compounds in the positive electrode material compositions of Examples 1-1 to 1-33, Examples 2-1 to 2-3, and Examples 3-1 to 3-23.

[0295] Table 3 shows performance data of the positive electrode active materials, positive electrode material compositions, positive electrode sheets, coin cells, and full cells of Examples 1-1 to 1-33 and Comparative Examples 1 to 8 measured according to the above-mentioned performance test method.

[0296] Table 4 shows performance data obtained by measuring the positive electrode active materials, positive electrode material compositions, positive electrode sheets, coin cells, and full cells of Examples 2-1 to 2-3 according to the above-mentioned performance test method.

[0297] Table 5 shows performance data obtained by measuring the positive electrode material compositions, positive electrode sheets, coin cells, and full cells of Examples 3-1 to 3-23 according to the above-mentioned performance test method.

[0298] [Table 1-1] [Table 1-2]

[0299] [Table 2]

[0300] [Table 3-1] [Table 3-2]

[0301] [Table 4]

[0302] [Table 5]

[0303] As can be seen from Examples 1-1 to 1-33 and Comparative Examples 1 to 8, the presence of the first coating layer is advantageous in reducing the Li / Mn antistructural defect concentration of the obtained material and the amount of Fe and Mn eluted after cycling, improving the gram capacity of the battery, and improving the safety performance and cycle performance of the battery. Doping the Mn site and phosphorus site with other elements can significantly reduce the lattice change rate, antistructural defect concentration, and amount of Fe and Mn eluted of the obtained material, improving the gram capacity of the battery, and improving the safety performance and cycle performance of the battery. After using the positive electrode active materials of Examples 1-1 to 1-33 in combination with an organopolysiloxane compound, the corrosion of the electrolyte on the surface of the positive electrode active material can be further alleviated and the amount of Fe and Mn eluted can be reduced, so that the cycle performance of the battery can be further improved.

[0304] As can be seen from Examples 1-2 to 1-6, as the amount of the first coating layer increases from 3.2% to 6.4%, the Li / Mn antistructural defect concentration of the resulting material gradually decreases, the amount of Fe and Mn eluted after cycling gradually decreases, and the safety performance and cycle performance at 45°C of the corresponding battery are also improved, but the gram capacity is slightly decreased. Alternatively, when the total amount of the first coating layer is 4 wt% to 5.6 wt%, the overall performance of the corresponding battery is optimal.

[0305] As can be seen from Example 1-3 and Example 1-7 to Example 1-10, as the amount of the second coating layer increases from 1% to 6%, the amount of Fe and Mn eluted from the obtained material after cycling gradually decreases, and the safety performance and cycle performance at 45°C of the corresponding battery are also improved, but the gram capacity is slightly decreased. Alternatively, when the total amount of the second coating layer is 3wt% to 5wt%, the overall performance of the corresponding battery is optimal.

[0306] As can be seen from Examples 1-11 to 1-15 and Comparative Examples 5 to 6, in the first coating layer, Li 2 FeP 2 O 7 and LiFePO 4 exist simultaneously, especially Li 2FeP 2 O 7 and LifePO 4 When the weight ratio is 1:3 to 3:1, and particularly 1:3 to 1:1, the improvement in battery performance is more remarkable.

[0307] Figure 7 is a comparison diagram between the XRD spectrum of the positive electrode active material core prepared in Example 1-1 and the XRD standard spectrum of lithium manganese phosphate (00-033-0804). As shown in Figure 7, the position of the main characteristic peak of the positive electrode active material core of the present application is almost the same as that of the lithium manganese phosphate doped, which indicates that the positive electrode active material core of the present application has no impurity phase, and the improvement of secondary battery performance is mainly due to element doping, not the impurity phase.

[0308] As can be seen from Table 4, with the gradual increase in the crystallinity of the pyrophosphate and phosphate in the first coating layer, the lattice change rate of the corresponding material, the Li / Mn antistructural defect concentration, and the amount of Fe and Mn dissolved are gradually decreased, the gram capacity of the battery is gradually increased, and the safety performance and cycle performance are also gradually improved.

[0309] As can be seen from Table 5, when the positive electrode active material is the same, by selecting an organopolysiloxane compound that satisfies one or more of the appropriate polar functional group content, number average molecular weight, and additive amount and using it in combination with the positive electrode active material, the cycle performance of the battery can be further improved, provided that the energy density and dynamic performance are not affected.

[0310] As can be further seen from Example 1-1, Example 3-1 to Example 3-5, as the amount of added organopolysiloxane compound increases, the powder resistance of the positive electrode active material composition decreases and then increases.The possible reason is that when the amount of added organopolysiloxane compound is within a certain range, it has hydrophobicity, so that it can reduce the interaction between conductive agents and mitigate the aggregation of conductive agents, thereby forming a better conductive network.

[0311] The present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is an example, and any configuration that has substantially the same technical idea and produces similar effects within the technical scope of the present application is included in the technical scope of the present application. In addition, various modifications to the embodiment that a person skilled in the art can conceive, and other forms constructed by combining some of the components in the embodiment, are also included in the scope of the present application, within the scope of the present application, without departing from the spirit of the present application.

Claims

1. A positive electrode material composition comprising a positive electrode active material having a core-shell structure and an organopolysiloxane compound, The positive electrode active material includes a core and a shell that covers the core, The core is Li 1+x Mn 1-y A y P 1-z R z O 4 wherein x is -0.100 to 0.100, and optionally -0.100 to 0.006; y is 0.001 to 0.500, and optionally 0.100 to 0.450; z is 0.001 to 0.100; A is one or more selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and optionally one or more selected from Fe, Ti, V, Ni, Co, and Mg; and R is one or more selected from B, Si, N, and S; The shell includes a first coating layer that coats the core and a second coating layer that coats the first coating layer, the first coating layer being made of pyrophosphate MP 2 O 7 and phosphate XPO 4 wherein M and X are each independently one or more selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and the second coating layer contains carbon; Positive electrode material composition.

2. The organopolysiloxane compound contains at least one structural unit represented by formula 1, [0010] R 1 , R 2 each independently represents at least one of the group consisting of functional groups selected from the group consisting of -COOH, -OH, -SH, -CN, -SCN, an amino group, a phosphate ester group, a carboxylate group, an amide group, an aldehyde group, a sulfonyl group, a polyether segment, a C1 to C20 aliphatic hydrocarbon group, a C1 to C20 halogenated aliphatic hydrocarbon group, a C1 to C20 heteroaliphatic hydrocarbon group, a C1 to C20 halogenated heteroaliphatic hydrocarbon group, a C6 to C20 aromatic hydrocarbon group, a C6 to C20 halogenated aromatic hydrocarbon group, a C2 to C20 heteroaromatic hydrocarbon group, and a C2 to C20 halogenated heteroaromatic hydrocarbon group, or H; Optionally, R 1 , R 2 each independently represents at least one of the functional groups selected from the group consisting of -COOH, -OH, -SH, an amino group, a phosphate ester group, a polyether segment, a C1-C8 alkyl group, a C1-C8 halogenated alkyl group, a C1-C8 heteroalkyl group, a C1-C8 halogenated heteroalkyl group, a C2-C8 alkenyl group, a C2-C8 halogenated alkenyl group, and a phenyl group, or H; More optionally, R 1 , R 2 each independently represents at least one of the functional groups selected from the group consisting of -OH, -SH, an amino group, a phosphate ester group, a polyether segment, a C1-C8 alkyl group, a C1-C8 halogenated alkyl group, a C1-C8 heteroalkyl group, a C1-C8 halogenated heteroalkyl group, a C2-C8 alkenyl group, and a C2-C8 halogenated alkenyl group, or H; The positive electrode material composition according to claim 1 .

3. The organopolysiloxane compound includes one or more types selected from a polysiloxane having a linear structure and a polysiloxane having a cyclic structure, and optionally, the organopolysiloxane compound is selected from a polysiloxane having a linear structure. The positive electrode material composition according to claim 1 or 2.

4. The linear polysiloxane further comprises a blocking group, optionally comprising at least one of the group consisting of polyether, C1-C8 alkyl group, C1-C8 halogenated alkyl group, C1-C8 heteroalkyl group, C1-C8 halogenated heteroalkyl group, C2-C8 alkenyl group, C2-C8 halogenated alkenyl group, C6-C20 aromatic hydrocarbon group, C1-C8 alkoxy group, C2-C8 epoxy group, hydroxyl group, C1-C8 hydroxyalkyl group, amino group, C1-C8 aminoalkyl group, carboxyl group, and C1-C8 carboxyalkyl group; The positive electrode material composition according to claim 3 .

5. The linear polysiloxane is, for example, polydimethylsiloxane, polydiethylsiloxane, polymethylethylsiloxane, polymethylvinylsiloxane, polyphenylmethylsiloxane, polymethylhydrogensiloxane, carboxyl-functionalized polysiloxane, polymethylchloropropylsiloxane, polymethyltrifluoropropylsiloxane, perfluorooctylmethylpolysiloxane, mercaptopropylpolysiloxane, aminoethylaminopropylpolydimethylsiloxane, methoxy-terminated polydimethylsiloxane, hydroxypropyl-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane, epoxy-terminated polysiloxane, hydroxy-terminated polydimethylsiloxane, polyether-terminated poly ... and / or one or more of: polydimethylsiloxane, side chain aminopropyl polysiloxane, side chain hydroxylmethyl polysiloxane, side chain hydroxylpropyl polysiloxane, side chain polyether grafted polydimethylsiloxane, and side chain phosphate ester grafted polydimethylsiloxane, optionally one or more of: polydimethylsiloxane, polymethylchloropropyl siloxane, polymethyltrifluoropropyl siloxane, mercaptopropyl polysiloxane, aminoethylaminopropyl polydimethylsiloxane, terminal hydroxydimethylsiloxane, terminal polyether polydimethylsiloxane, and side chain phosphate ester grafted polydimethylsiloxane; and / or The polysiloxane having a cyclic structure includes one or more of cyclic polydimethylsiloxane, cyclic polymethylvinylsiloxane, cyclic polymethylhydrogensiloxane, and cyclic polymethyltrifluoropropylsiloxane, and optionally includes one or more of 1,3,5,7-octamethylcyclotetrasiloxane, 1,3,5,7-tetrahydro-1,3,5,7-tetramethylcyclotetrasiloxane, cyclopentapolydimethylsiloxane, 2,4,6,8-tetramethylcyclotetrasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, hexadecamethyloctasiloxane, and tetradecamethylcycloheptasiloxane. The positive electrode material composition according to claim 3 or 4.

6. The number average molecular weight of the organopolysiloxane compound is 300,000 or less, and optionally 400 to 80,000; The positive electrode material composition according to claim 1 .

7. The weight percentage of polar functional groups in the organopolysiloxane compound is α, 0≦α<50%, and optionally 5%≦α≦30%; The positive electrode material composition according to claim 1 .

8. the content of the organopolysiloxane compound is 0.01% to 2% by weight, optionally 0.1% to 2% by weight, calculated based on the total weight of the positive electrode material composition; The positive electrode material composition according to claim 1 .

9. The coverage of the first coating layer is greater than 0% and less than or equal to 7% by weight, optionally between 4% and 5.6% by weight, calculated based on the weight of the core; and / or The coating amount of the second coating layer is greater than 0% and not more than 6% by weight, optionally 3% to 5% by weight, calculated based on the weight of the core; The positive electrode material composition according to claim 1 .

10. The phosphate of the first coating layer has a lattice spacing of 0.345 nm to 0.358 nm and an included angle of the (111) crystal orientation of 24.25° to 26.45°; and / or The pyrophosphate of the first coating layer has a lattice spacing of 0.293 nm to 0.326 nm and an included angle of the crystal orientation (111) of 26.41° to 32.57°. The positive electrode material composition according to claim 1 .

11. in said core, the ratio of y to 1-y is from 1:10 to 10:1, optionally from 1:4 to 1:1; and / or In the core, the ratio of z to 1-z is from 1:9 to 1:999, optionally from 1:499 to 1:249; The positive electrode material composition according to claim 1 .

12. the weight ratio of pyrophosphate to phosphate in the first coating layer is from 1:3 to 3:1, optionally from 1:3 to 1:1; and / or The crystallinity of the pyrophosphate and the phosphate in the first coating layer is independently 10% to 100%, and optionally 50% to 100%; The positive electrode material composition according to claim 1 .

13. The A is at least two selected from Fe, Ti, V, Ni, Co and Mg; The positive electrode material composition according to any one of claims 1 to 12.

14. The positive electrode active material satisfies at least one of the following conditions (1) to (4): (1) the positive electrode active material has a Li / Mn antistructure defect concentration of 4% or less, and optionally 2% or less; (2) The lattice change rate of the positive electrode active material is 8% or less, and optionally 4% or less; (3) the valence of the surface oxygen of the positive electrode active material is −1.88 or less, and optionally −1.98 to −1.88; (4) The compaction density per 3 tons of the positive electrode active material is 2.0 g / cm 3 or more, optionally 2.2 g / cm 3 That's all. The positive electrode material composition according to any one of claims 1 to 13.

15. Further comprising a conductive agent and an adhesive, optionally the content of the adhesive is 1.79 wt % to 10 wt %, calculated based on the total weight of the positive electrode material composition, and optionally the content of the conductive agent is 0.2 wt % to 10 wt %, calculated based on the total weight of the positive electrode material composition. The positive electrode material composition according to claim 1 .

16. and / or the powder resistivity of the positive electrode material composition at 12 MPa is 4 Ω / cm to 55 Ω / cm, optionally 4 Ω / cm to 40 Ω / cm; and The specific surface area of ​​the positive electrode material composition is 8 m 2 / g to 20m 2 / g, optionally 8m 2 / g to 15m 2 / g, The positive electrode material composition according to any one of claims 1 to 15.

17. A method for producing a positive electrode material composition, comprising the steps of: Providing a core material, the core comprising Li 1+x Mn 1-y A y P 1-z R z O 4 providing a core material comprising: x is -0.100 to 0.100, optionally -0.100 to 0.006; y is 0.001 to 0.500, optionally 0.100 to 0.450; z is 0.001 to 0.100; A is one or more selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, optionally one or more of Fe, Ti, V, Ni, Co and Mg; and R is one or more selected from B, Si, N and S; A coating process comprising: 2 O 7 Powder and XPO containing a carbon source 4 providing a suspension, said core material and MP 2 O 7 The powder was mixed with XPO containing a carbon source. 4 and adding the resulting mixture to the suspension, mixing and sintering to obtain a positive electrode active material, wherein M and X are each independently one or more selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al, and the obtained positive electrode active material has a core-shell structure including the core and a shell covering the core, the shell including a first covering layer covering the core and a second covering layer covering the first covering layer, and the first covering layer is pyrophosphate MP 2 O 7 and phosphate XPO 4 wherein the second coating layer comprises carbon; A mixing step of uniformly mixing the obtained positive electrode active material with an organopolysiloxane compound, an optional adhesive, and an optional conductive agent to obtain a positive electrode material composition. A method for producing a positive electrode material composition.

18. The step of providing a core material comprises: A step (1) of mixing and stirring a manganese source, an element A source, and an acid in a container to obtain manganese salt particles doped with element A; The manganese salt particles doped with element A are mixed with a lithium source, a phosphorus source and an element R source in a solvent to obtain a slurry, which is then sintered under the protection of an inert gas atmosphere to obtain lithium manganese phosphate doped with element A and element R, wherein the lithium manganese phosphate doped with element A and element R is Li 1+x Mn 1-y A y P 1-z R z O 4 and step (2) in which x is -0.100 to 0.100, and optionally -0.100 to 0.006, y is 0.001 to 0.500, and optionally 0.100 to 0.450, z is 0.001 to 0.100, A is one or more selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and optionally one or more selected from Fe, Ti, V, Ni, Co, and Mg, and R is one or more selected from B, Si, N, and S.

20. The method of claim 17.

19. Step (1) is carried out at a temperature between 20° C. and 120° C., optionally between 25° C. and 80° C.; and / or The stirring in step (1) is carried out at 500 rpm to 700 rpm for 60 minutes to 420 minutes, optionally for 120 minutes to 360 minutes; 20. The method of claim 18.

20. the element A source is one or more selected from the group consisting of a simple substance, a sulfate, a halide, a nitrate, an organic acid salt, an oxide, and a hydroxide of the element A, and / or the element R source is one or more selected from the group consisting of a simple substance, a sulfate, a halide, a nitrate, an organic acid salt, an oxide, and a hydroxide of the element R, and an inorganic acid of the element R; 20. The method of claim 18 or 19.

21. The MP 2 O 7 The powder is produced by the following method: adding an element M source and a phosphorus source to a solvent to obtain a mixture, adjusting the pH of the mixture to 4-6, stirring to fully react, and then drying and sintering the mixture, where M is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al; 21. The method according to any one of claims 17 to 20.

22. The drying step is performed at 100° C. to 300° C., optionally 150° C. to 200° C., for 4 hours to 8 hours, and / or The sintering step is performed at 500° C. to 800° C., optionally 650° C. to 800° C., for 4 hours to 10 hours under an inert gas atmosphere; and / or The sintering temperature for obtaining the positive electrode active material in the coating process is 500° C. to 800° C., and the sintering time is 4 hours to 10 hours.

22. The method of claim 21.

23. A positive electrode sheet, A positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector, the positive electrode film layer comprising the positive electrode material composition according to any one of claims 1 to 16 or the positive electrode material composition produced by the method according to any one of claims 17 to 22, and a content of the positive electrode material composition in the positive electrode film layer is 50 wt% or more, and optionally 90 wt% to 100 wt%, calculated based on a total weight of the positive electrode film layer. Positive electrode sheet.

24. The positive electrode sheet satisfies at least one of the following conditions (1) to (6): (1) the solid-liquid contact angle between the positive electrode film layer and the nonaqueous organic solvent is 3° to 90°, optionally 3° to 60°, further 10° to 30°; (2) the porosity of the positive electrode membrane layer is 15% to 50%, optionally 15% to 30%; (3) The resistance of the positive electrode film layer is greater than 0 and less than or equal to 6 Ω. (4) The adhesive strength between the positive electrode film layer and the positive electrode current collector is 0.5 MPa or more. (5) The surface density of the positive electrode film layer is 0.006 g / cm 2 ~0.065g / cm 2 That is, (6) The positive electrode membrane layer has an electrolyte absorption rate of 0.0125 μg / s to 100 μg / s, and optionally 0.5 μg / s to 40 μg / s; The positive electrode sheet according to claim 23.

25. A positive electrode material composition according to any one of claims 1 to 16, or a positive electrode material composition produced by the method according to any one of claims 17 to 22, or a positive electrode sheet according to claim 23 or 24. Secondary battery.

26. The secondary battery according to claim 25, Power consumption equipment.

Citation Information

Patent Citations

  • Manganese-iron-lithium phosphate material and preparation method thereof, battery paste, cathode and lithium battery

    CN106816600A

  • Binder composition for electrode, slurry for electrode, electrode, and power storage device

    JP2014110195A

  • Positive electrode active material for lithium ion secondary battery, positive electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2016149357A